Film, laminated film, and method for producing film

By forming protrusions with relatively low heights on the surface of the resin layer of the film, the problem of prone to concave and convex defects on the surface of the functional layer after film is wound, and better transportability and smoothness of the functional layer are achieved.

CN119789950APending Publication Date: 2025-04-08FUJIFILM CORP
View PDF 18 Cites 0 Cited by

Patent Information

Application Number
CN202380062073.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-26
Filing Date
2023-08-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the process of conveying the film and configuring the functional layer on its surface, when the film is wound and rolled out, it is easy to cause concave and convex defects on the surface of the functional layer, affecting the function and use effect of the functional layer.

Method used

By forming a protrusion having a specific height and shape on the surface of the resin layer of the film, the ratio of the height of the protrusion to the length and diameter is 0.70 or less, so as to reduce the fall of the protrusion and the concave and convex defects of the functional layer.

Benefits of technology

It effectively suppresses the concave and convex defects on the surface of the functional layer when it is rolled out, improves the conveying ability of the film and the smoothness of the functional layer, and ensures the function and performance of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119789950A_ABST
    Figure CN119789950A_ABST
Patent Text Reader

Abstract

The present invention addresses the problem of providing a film in which a functional layer is disposed on one surface of the film while the film is being conveyed, and when the obtained film is wound and then unwound, irregularities do not easily occur on the surface of the functional layer. This film comprises a resin substrate and a resin layer, the resin layer having protrusions on the surface thereof, and the ratio of the height of the protrusions to the major axis of the protrusions being 0.70 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a film, a laminated film and a method for producing the film. Background Art

[0002] Films having excellent smoothness and sliding properties are used in various applications. Films having such properties are used, for example, in touch panel films, optical component films, molding substrates, decorative film substrates, and photosensitive layer substrates.

[0003] The film having the above-mentioned properties is often produced by providing protrusions derived from particles on at least one surface of the film.

[0004] For example, Patent Document 1 describes that a biaxially oriented film is produced by applying a coating liquid in which acrylic particles are dispersed in water onto one surface of a thermoplastic resin film (resin substrate).

[0005] Patent Document 2 describes that a film is obtained by applying a coating liquid containing a solvent and resin particles onto one surface of a polyester film (resin substrate).

[0006] Previous technical literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2005-015539

[0009] Patent Document 2: Japanese Patent Application Publication No. 2014-223784 Summary of the invention

[0010] Technical issues to be solved by the invention

[0011] On the other hand, when a layer (functional layer) for developing a specific function is provided on the film as described above, the functional layer is often formed while the film is conveyed. Furthermore, the film having the functional layer formed thereon is usually rolled up after the functional layer is formed, and is unrolled when the film is used.

[0012] The present inventors have found that, for the films described in Patent Documents 1 and 2, when the functional layer is formed while being conveyed and the obtained film is wound up, concavo-convex defects may be generated on the surface of the functional layer when the film is unwound. If the concavo-convex defects as described above are generated on the surface of the functional layer, the function of the functional layer and the product formed using the functional layer are affected, and therefore it is desired to suppress the generation of the concavo-convex defects.

[0013] Therefore, an object of the present invention is to provide a film in which a functional layer is arranged on one surface of a film while the film is being conveyed, and when the obtained film is wound up and then unwound, uneven defects are less likely to occur on the surface of the functional layer.

[0014] Another object of the present invention is to provide a laminated film including a film and a functional layer. Another object of the present invention is to provide a method for producing a film.

[0015] Means for solving technical problems

[0016] The present inventors have conducted intensive studies to solve the above-mentioned problems and have completed the present invention. Specifically, they have found that the above-mentioned problems can be solved by the following configurations.

[0017] [1] A film comprising a resin substrate and a resin layer,

[0018] The resin layer has protrusions on its surface.

[0019] The ratio of the height of the protrusion to the major diameter of the protrusion is 0.70 or less.

[0020] [2] The film according to [1], wherein

[0021] The protrusions include a non-polyester resin.

[0022] [3] The film according to [1] or [2], wherein

[0023] The protrusions include at least one of an acrylic resin and a styrene resin.

[0024] [4] The film according to any one of [1] to [3], wherein

[0025] The resin layer is a single-layer coating layer.

[0026] [5] The film according to any one of [1] to [4], wherein

[0027] The resin layer includes at least one binder selected from acrylic resins, urethane resins, and olefin resins.

[0028] [6] The film according to [5], wherein

[0029] The above-mentioned binder contains a resin having an acid group.

[0030] [7] The film according to any one of [1] to [6], wherein

[0031] The resin layer is a cross-linked film.

[0032] [8] The film according to any one of [1] to [7], wherein

[0033] The thickness of the resin layer is 0.01 to 1 μm.

[0034] [9] The film according to any one of [1] to [8], wherein

[0035] The protrusions are 10000 μm thick on the surface of the resin layer. 2 There are more than 50 in the area.

[0036]

[10] The film according to any one of [1] to [9], wherein

[0037] The ratio of the major diameter of the protrusion to the minor diameter of the protrusion exceeds 1.60.

[0038]

[11] A laminated film comprising the film according to any one of [1] to

[10] and a functional layer,

[0039] The laminated film comprises the resin layer, the resin substrate and the functional layer in this order.

[0040] The functional layer is one selected from a decorative layer, a photosensitive resin layer, an inorganic layer and a release layer.

[0041]

[12] A method for producing a film, comprising the following steps:

[0042] A step of forming a layer on at least one surface of a resin substrate using a composition comprising non-crosslinked resin particles A, resin B, and a solvent; and

[0043] The method for producing the film comprises the step of stretching the resin substrate having the layer formed thereon while heating it at a temperature Y, and the method satisfies the following requirements 1 and 2.

[0044] Requirement 1: The value obtained by subtracting the glass transition temperature of the non-crosslinked resin particles A from the temperature Y is -20 to 50°C.

[0045] Requirement 2: When the resin B is present in the composition in the form of particles, the particle size of the resin B in the form of particles is smaller than the particle size of the non-crosslinked resin particles A.

[0046]

[13] The method for producing a film according to

[12] , wherein:

[0047] The resin substrate is a uniaxially oriented resin substrate obtained by stretching an unstretched resin substrate.

[0048]

[14] The method for producing a film according to

[12] or

[13] , wherein:

[0049] The resin B is a resin having an acid group, and the composition further includes a cross-linking agent.

[0050]

[15] The method for producing a film according to any one of

[12] to

[14] , wherein:

[0051] The non-crosslinked resin particles A have a glass transition temperature of 70 to 140°C.

[0052]

[16] The method for producing a film according to any one of

[12] to

[15] , wherein:

[0053] The glass transition temperature of the resin B is -50 to 105°C.

[0054]

[17] The method for producing a film according to any one of

[12] to

[16] , wherein:

[0055] When the resin B is present in the composition in the form of particles, the particle size of the resin B is Db μm, and the particle size of the non-crosslinked resin particles A is Da, the relationship of formula (1) is satisfied.

[0056] Formula (1) 7×Db <Da

[0057] Effects of the Invention

[0058] According to the present invention, a film can be provided in which a functional layer is disposed on one surface of a film while the film is conveyed, and when the obtained film is wound up and then unwound, uneven defects are less likely to occur on the surface of the functional layer.

[0059] Furthermore, according to the present invention, a laminated film including a film and a functional layer can be provided. Furthermore, according to the present invention, a method for producing a film can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] Figure 1 This is a cross-sectional view showing an example of the structure of the film of the present invention.

[0061] Figure 2 This is an observed image of the surface of a biaxially oriented film produced by a method similar to that of Example.

[0062] Figure 3 This is an observed image of the surface of a biaxially oriented film produced by a method similar to that of the comparative example. DETAILED DESCRIPTION

[0063] Hereinafter, the present invention will be described in detail.

[0064] Although the description of the constituent elements described below may be made based on representative embodiments of the present invention, the present invention is not limited to such embodiments.

[0065] The meaning of each description in this specification is shown below.

[0066] In this specification, the numerical range represented by "~" refers to a range that includes the numerical values ​​recorded before and after "~" as the lower limit and upper limit. In the numerical range recorded in stages in this specification, the upper limit or lower limit recorded in a certain numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical range recorded in this specification, the upper limit or lower limit recorded in a certain numerical range can also be replaced by the value shown in the embodiment.

[0067] In the present specification, when a plurality of substances corresponding to each component are present in a composition, the amount of each component in the composition refers to the total amount of the plurality of substances present in the composition unless otherwise specified.

[0068] In the present specification, the term "process" includes not only an independent process but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process can be achieved.

[0069] In the present specification, a combination of two or more preferred aspects is a more preferred aspect.

[0070] In this specification, the "longitudinal direction" refers to the longitudinal direction of a film when the film is produced, and has the same meaning as the "conveying direction" and the "machine direction".

[0071] In this specification, "width direction" refers to a direction orthogonal to the length direction. In this specification, "orthogonal" is not limited to strictly orthogonal, and includes substantially orthogonal. "Substantially orthogonal" means intersecting within the range of 90°±5°, preferably intersecting within the range of 90°±3°, and more preferably intersecting within the range of 90°±1°.

[0072] In this specification, "long diameter" refers to the longest diameter of the protrusion in the in-plane direction when observing the protrusion existing on the film surface. More specifically, the distance between two parallel lines selected in such a way that the distance between parallel lines becomes the largest when observing the protrusion is circumscribed to the shape of the protrusion in the in-plane direction.

[0073] In this specification, "minor diameter" refers to the longest diameter of the protrusion in the in-plane direction in a direction orthogonal to the longest diameter (major diameter) of the protrusion in the in-plane direction when observing the protrusion existing on the film surface. More specifically, the distance between two parallel lines that are orthogonal to the two parallel lines that give the above-mentioned major diameter and are circumscribed to the shape of the protrusion in the in-plane direction is selected so that the distance between the parallel lines becomes the smallest, which is set as the minor diameter.

[0074] [membrane]

[0075] The film of the present invention (hereinafter also referred to simply as "the present film") is a film comprising a resin substrate and a resin layer, wherein the resin layer has protrusions on its surface, and the ratio of the height of the protrusions to the major diameter of the protrusions is 0.70 or less.

[0076] The structure of the present film will be described with reference to the drawings.

[0077] Figure 1 1 is a cross-sectional view showing an example of the structure of the present film. The film 1 of the present invention comprises a resin layer 2 and a resin substrate 3, and has a first main surface 4 and a second main surface 5. The second main surface 5 is one of the surfaces of the resin layer 2, and the resin layer 2 has a protrusion 6 on the surface serving as the second main surface 5. A functional layer not shown in the figure can be provided on the first main surface 4. In addition, the ratio of the height of the protrusion 6 to the major diameter of the protrusion 6 is 0.70 or less.

[0078] Although the detailed mechanism of why uneven defects are less likely to occur on the surface of the functional layer when the film is conveyed while a functional layer is arranged on one surface of the film and the obtained film is wound up and then unwound is not necessarily clear, the present inventors speculate as follows.

[0079] When the film is conveyed, the film contacts other parts such as a conveying roller. From the viewpoint of the conveyability of the film, it is believed that when protrusions are provided on the surface of the film, the protrusions on the film surface or a part of the film including the protrusions may fall off in the form of particles due to the impact caused by the contact between the surface of the film having the protrusions and other parts such as a conveying roller.

[0080] As described above, if the particles fall off, the particles may be attached to the surface of the film on the side opposite to the side with the protrusion when the film is wound up before the functional layer is formed. In this state, if the functional layer is formed on the surface of the film on the side opposite to the side with the protrusion, the attached particles may become foreign matter and form convex portions on the functional layer. Furthermore, if the above-mentioned particles that become foreign matter in the functional layer fall off from the functional layer, concave portions may be formed on the functional layer.

[0081] Furthermore, as described above, if the particles fall off, the particles may be attached to the surface of the side of the film with the protrusion. In this state, if the film is wound up to form a functional layer, the particles are transferred to the surface of the functional layer, and when the film is unwound, the particles are attached to the surface of the functional layer, and a convex portion may be formed on the functional layer. Furthermore, the particles are pressed into the functional layer due to the pressure acting during winding and storage, and a concave portion may be formed on the functional layer.

[0082] On the other hand, if the film obtained by forming the functional layer is rolled up in a state where the particles are easily generated as described above, the particles may be transferred to the surface of the functional layer. When the film is rolled out in this state, the particles will be attached to the surface of the functional layer, and a convex portion may be formed on the functional layer.

[0083] The film comprises a resin substrate and a resin layer, and the resin layer has protrusions on its surface. It is believed that through the above structure, not only the part constituting the protrusions is attached to the resin substrate as in Patent Documents 1 and 2, but also the part constituting the protrusions can be held by the resin layer, so that the part constituting the protrusions is not easy to fall off in the form of particles.

[0084] Moreover, in this film, the ratio of the height of the protrusion to the major diameter of the protrusion is less than 0.70. It is believed that in the case of the above structure, the protrusion is relatively flat, and the contact area between the bottom surface of the protrusion and the resin layer becomes larger. In this way, it is believed that the part constituting the protrusion is less likely to fall off in the form of particles, and as a result, it is less likely to produce concave-convex defects on the surface of the functional layer.

[0085] In addition, hereinafter, the case where the functional layer is arranged on one surface of the film while the present film is conveyed, and the obtained film is wound up and then unwound, and uneven defects are less likely to occur on the surface of the functional layer is also referred to as "suppressing uneven defects".

[0086] 〔structure〕

[0087] The structure of the present film will be described below.

[0088] The film comprises at least a resin substrate and a resin layer, wherein the resin layer has protrusions on its surface, and the ratio of the protrusion height to the protrusion major diameter is 0.70 or less. The ratio of the protrusion height to the protrusion major diameter will be described later.

[0089] Furthermore, the present film has a first main surface and a second main surface.

[0090] Of the two main surfaces of the present film, the first main surface is a surface on which a functional layer described below can be formed. That is, after the present film is manufactured, the functional layer is formed on the first main surface, thereby manufacturing a laminated film having the film and the functional layer.

[0091] Of the two main surfaces of the resin substrate, the second main surface on the side opposite to the first main surface is one of the surfaces of the resin layer. That is, the resin layer constitutes the outermost layer of the present film. In other words, the present film is a film comprising a resin substrate and a resin layer, and has a protrusion on the surface of the resin layer on the side opposite to the resin substrate side.

[0092] The present film is not limited to a film having the above-mentioned structure as long as it has at least the above-mentioned resin substrate and the resin layer and satisfies the ratio related to the above-mentioned protrusions.

[0093] For example, the present film may include another layer such as a primer layer between the resin layer and the resin substrate.

[0094] Hereinafter, each layer included in the present film will be described in detail.

[0095] <Resin Layer>

[0096] The resin layer is a layer formed on one side of the resin substrate. The resin layer is continuously formed on one side of the resin substrate. In addition, a protrusion is formed on the surface of the resin layer on the side opposite to the surface facing the resin substrate.

[0097] The film has the above-mentioned resin layer, so that the transportability of the film and the laminated film is improved and uneven defects are suppressed.

[0098] The resin layer may be provided directly on the surface of the resin substrate or via another layer. However, it is preferably provided directly on the surface of the resin substrate from the viewpoint of better adhesion.

[0099] The resin layer is not particularly limited as long as it is a layered component having protrusions on at least one surface, but preferably contains an adhesive. As the adhesive contained in the resin layer, a non-polyester resin other than a polyester resin is preferred. In addition, the resin layer may contain additives other than the substance constituting the protrusion and the non-polyester resin.

[0100] In addition, in this specification, "binder" means a component including a resin other than a substance constituting the protrusions.

[0101] Furthermore, from the viewpoint of being able to suppress uneven defects, the resin layer is preferably a single layer. Furthermore, as described in the following paragraph, the resin layer is preferably a coating layer formed using a composition containing non-crosslinked resin particles A, resin B and a solvent. The "coating layer" refers to a layer formed by a process having the following treatment, which is a treatment formed by coating at least a liquid composition.

[0102] Furthermore, the resin layer is also preferably a single layer and a coating layer.

[0103] (Protrusion)

[0104] The material constituting the protrusions is not particularly limited, and may be a single material or a combination of two or more materials. Furthermore, the material constituting the protrusions may be the same as or different from the above-mentioned binder.

[0105] As the protrusions present on the surface of the resin layer, for example, protrusions formed by particles described later can be cited. From the viewpoint of being able to suppress concavo-convex defects and the viewpoint that the ratio of the height of the protrusion to the major diameter of the protrusion is easily 0.70 or less, protrusions formed by organic particles are preferred. In addition, although it is unclear about the detailed mechanism by which the concavo-convex defects can be further suppressed when the protrusions are formed by organic particles, it is speculated as follows. That is, it is speculated that when the film contacts the contacted object on the second main surface, the force borne by the protrusion is absorbed by the deformation of the protrusion, and as a result, it is less likely to cause the material constituting the protrusion to fall off, and as a result, the concavo-convex defects can be suppressed.

[0106] As organic particles, resin particles are preferred. As resins constituting the resin particles, for example, non-polyester resins can be cited, preferably styrene resins, urethane resins, acrylic resins, and silicone resins. Among them, from the viewpoint that the ratio of the height of the protrusion to the major diameter of the protrusion is easily 0.70 or less, the organic particles preferably contain at least one selected from styrene resins, acrylic resins, and urethane resins, and more preferably contain at least one selected from styrene resins and acrylic resins.

[0107] That is, the protrusions preferably contain the resin constituting the above-mentioned resin particles.

[0108] In this specification, a styrene resin refers to a resin containing a structural unit derived from styrene.

[0109] As the styrene resin constituting the resin particles, there can be mentioned homopolymers consisting only of styrene, and styrene copolymers such as styrene-acrylic acid copolymers containing structural units derived from styrene and structural units derived from acrylate or methacrylate. The styrene resin preferably contains structural units derived from styrene in an amount of 50 mol% or more relative to all structural units.

[0110] The urethane resin constituting the resin particles is not limited as long as it is a polymer having a urethane bond, and a known urethane resin such as a reaction product of an isocyanate compound and a polyol compound can be used.

[0111] In the present specification, an acrylic resin refers to a resin containing a structural unit derived from an acrylate or methacrylate ester. The acrylic resin preferably contains 50 mol% or more of a structural unit derived from an acrylate or methacrylate ester relative to all structural units.

[0112] The resin particles may be cross-linked resin particles having a cross-linked structure, but are preferably non-cross-linked resin particles having no cross-linked structure. Examples of the cross-linked resin particles include cross-linked urethane resin particles composed of urethane resin having a cross-linked structure. Examples of the non-cross-linked resin particles include non-cross-linked styrene resin particles composed of non-cross-linked styrene resin and non-cross-linked acrylic resin particles composed of non-cross-linked acrylic resin.

[0113] The resin particles may be used alone or in combination of two or more. That is, two or more non-crosslinked resin particles may be used in combination. Furthermore, non-crosslinked resin particles and crosslinked resin particles may be used in combination. When non-crosslinked resin particles and crosslinked resin particles are used in combination, the height of the protrusions formed by the non-crosslinked resin particles is preferably greater than the height of the protrusions formed by the crosslinked resin particles.

[0114] As a commercial item of styrene resin particles, Nipol (registered trademark) UFN1008 (produced by Zeon Corporation) is mentioned, for example.

[0115] Examples of commercially available products of urethane resin particles include ART PEARL (registered trademark) C-1000T and MM110SMA (manufactured by Negami Chemical Industrial Co., Ltd.).

[0116] As a commercial item of acrylic resin particles, MP1000 (made by Soken Chemical & Engineering Co., Ltd.) is mentioned, for example.

[0117] (Adhesive)

[0118] The resin layer preferably contains a non-polyester resin as a binder from the viewpoint of excellent effect of suppressing unevenness defects during long-term storage.

[0119] The non-polyester resin contained in the resin layer as a binder is not particularly limited as long as it is a resin other than a polyester resin, and examples thereof include acrylic resins, urethane resins, olefin resins, polyvinyl alcohol resins, and acrylonitrile-butadiene resins. From the viewpoint of achieving a more excellent effect of the present invention, acrylic resins, urethane resins, or olefin resins are preferred, and urethane resins are more preferred.

[0120] Here, since acrylic resins and olefin resins are not sufficiently compatible with polyester resins preferably used in resin substrates, it is estimated that foreign matter caused by impurities such as oligomers precipitated from polyester resins is not easily generated even when stored for a long time. In addition, it is believed that urethane resins with high hydrophobicity among urethane resins (i.e., urethane resins with a SP value greatly different from that of polyester resins) can also suppress uneven defects during long-term storage for the same reason as acrylic resins and olefin resins.

[0121] The acrylic resin, olefin resin, and urethane resin are not particularly limited, and known resins can be used.

[0122] The non-polyester resin contained as a binder in the resin layer is also preferably a resin having an acid group.

[0123] The olefin resin may be any resin containing a structural unit derived from an olefin in the main chain. The olefin is not particularly limited, but is preferably an alkene having 2 to 6 carbon atoms, more preferably ethylene, propylene or hexene, and still more preferably ethylene.

[0124] The content of the structural unit derived from olefin in the olefin resin is preferably 50 to 99 mol %, more preferably 60 to 98 mol %, based on all the structural units of the olefin resin.

[0125] As the olefin resin, an acid-modified olefin resin is preferred from the viewpoint of being able to suppress uneven defects during long-term storage. As the acid-modified olefin resin, for example, a copolymer obtained by modifying the above-mentioned olefin resin with an acid-modified component such as an unsaturated carboxylic acid or its anhydride can be cited. That is, the olefin resin is preferably an olefin resin having an acid group.

[0126] Examples of the acid-modified component include acrylic acid, methacrylic acid, maleic acid, maleic anhydride, itaconic acid, itaconic anhydride, fumaric acid and crotonic acid, and half esters and half amides of unsaturated dicarboxylic acids. From the perspective of dispersion stability of the resin, acrylic acid, methacrylic acid, maleic acid or maleic anhydride is preferred.

[0127] The acid groups contained in the acid-modified olefin resin include acid groups corresponding to the above-mentioned acid-modified components, carboxyl groups, sulfonic groups and phosphoric acid groups, preferably carboxyl groups. The acid groups may form acid anhydrides or may be neutralized by at least one selected from alkali metals, organic amines and ammonia.

[0128] The acid-modified olefin resin may contain only one type of structural unit having an acid group, or may contain two or more types.

[0129] Examples of commercially available acid-modified olefin resins include ZAIKTHENE (registered trademark) series such as ZAIKTHENE AC, A, L, NC, and N (manufactured by SUMITOMO SEIKA CHEMICALS CO., LTD.), CHEMIPEARL (registered trademark) series such as CHEMIPEARL S100, S120, S200, S300, S650, and SA100 (manufactured by Mitsui Chemicals, Inc.), and Hi-tech (registered trademark) series such as Hi-tech S3121 and S3148K (manufactured by TOHO Chemical Industry Co., Ltd.), ARROW BASE (registered trademark) series such as ARROW BASE SE-1013, SE-1010, SB-1200, SD-1200, SD-1200, DA-1010, and DB-4010 (manufactured by UNITIKA LTD.), HARDLEN AP-2, NZ-1004, NZ-1005 (manufactured by TOYOBO CO., LTD.), Seporjon G315, VA407 (manufactured by SUMITOMO SEIKA CHEMICALS CO., LTD.).

[0130] Furthermore, the acid-modified olefin resins described in

[0022] to

[0034] of JP-A-2014-076632 can also be preferably used.

[0131] The acrylic resin is a resin containing a structural unit derived from a (meth)acrylate, and can be copolymerized with a vinyl monomer such as styrene. The acrylic resin is not particularly limited, but preferably contains a structural unit derived from a (meth)acrylate having an alkyl group with 1 to 12 carbon atoms, and more preferably contains a structural unit derived from a (meth)acrylate having an alkyl group with 1 to 8 carbon atoms.

[0132] From the viewpoint of being able to suppress uneven defects during long-term storage, the acrylic resin preferably has an acid-modified component. Furthermore, the acrylic resin preferably contains a structural unit derived from (meth)acrylic acid. That is, the acrylic resin is preferably an acrylic resin having an acid group.

[0133] (Meth)acrylic acid may be in the form of anhydride or may be neutralized with at least one selected from an alkali metal, an organic amine and ammonia.

[0134] When an aqueous dispersion of an acrylic resin is used for producing the resin layer, an aqueous dispersion containing an acrylic resin and a dispersant can be preferably used.

[0135] The content of the structural unit derived from (meth)acrylate in the acrylic resin is preferably 50 to 100 mol % based on all the structural units in the acrylic resin.

[0136] The acid value of the acrylic resin is preferably 30 mgKOH / g or less, more preferably 20 mgKOH / g or less. The lower limit of the acid value is not particularly limited, and is, for example, 0 mgKOH / g, but is preferably 2 mgKOH / g or more from the viewpoint of coating in the form of a water dispersion.

[0137] When an acrylic resin having a solubility parameter (SP value) different from that of a polyester resin is used, the compatibility of the acrylic resin and the polyester resin becomes insufficient, and as a result, the effect of suppressing uneven defects during long-term storage can be further improved. Such an acrylic resin can be obtained by adjusting the acid value to be within the above range and containing a structural unit derived from a (meth)acrylate having an alkyl group having 1 to 12 carbon atoms.

[0138] The urethane resin is not limited as long as it is a polymer having a urethane bond, and a known urethane resin such as a reaction product of an isocyanate compound and a polyol compound can be used.

[0139] When a water dispersion containing a urethane resin is used for producing the resin layer, the water dispersion preferably contains a urethane resin having an acidic group (eg, a carboxyl group), or contains a urethane resin and a dispersant. This improves the film-forming properties of the resin layer.

[0140] The urethane resin can be made into a desired SP value by adjusting at least one of the structure of the polyol compound as a raw material, the hydrophobicity or hydrophilicity of the polyol as a raw material, the structure of the isocyanate compound as a raw material, and the hydrophobicity or hydrophilicity of the isocyanate compound as a raw material. In this way, by using a urethane resin adjusted to have a higher hydrophobicity, the compatibility of the urethane resin and the polyester resin becomes insufficient, and as a result, the effect of suppressing uneven defects during long-term storage can be further improved.

[0141] Among the urethane resins, urethane resins having a polyester structure (polyester-based urethane resins) are preferred because they have high hydrophobicity and can further enhance the effect of suppressing unevenness defects during long-term storage.

[0142] Examples of commercially available urethane resins include HYDRAN (registered trademark) AP-40N, HW-312B, and HW-350 (all manufactured by DIC Corporation), TAKELAC (registered trademark) W-5030 and W-6020 (all manufactured by Mitsui Chemicals, Inc.), ADEKABON TITER (registered trademark) HUX-524 (manufactured by ADEKA CORPORATION), and SUPERFLEX (registered trademark) 210 (manufactured by DKS Co., Ltd.).

[0143] The resin layer may contain a single non-polyester resin as a binder, or may contain two or more non-polyester resins.

[0144] From the viewpoint of further suppressing uneven defects, the content of the binder in the resin layer is preferably 30 to 99.8% by mass, more preferably 50 to 99.5% by mass, based on the total mass of the resin layer.

[0145] Furthermore, the binder contained in the resin layer is preferably crosslinked by a crosslinking agent described later, etc. That is, the resin layer is preferably a crosslinked film. When the resin layer is a crosslinked film, the resin layer may be completely crosslinked, or the resin layer may have an uncrosslinked region.

[0146] As an example of a resin layer being a cross-linked film, in the case where protrusions are formed by the method described later and non-cross-linked resin particles are used, a method in which non-cross-linked resin particles and an adhesive are cross-linked by a cross-linking agent to form a cross-linked film can be cited. In the case where the non-cross-linked resin particles and the adhesive are cross-linked by a cross-linking agent, a chemical bond between the resin particles and the adhesive is formed in the protrusion formed as a result, so it is less likely to cause the material constituting the protrusion to fall off, and it is possible to further suppress uneven defects, and the solvent resistance is also excellent. In addition, when the resin layer is a cross-linked film, the precipitation of oligomers is suppressed, and uneven defects during long-term storage can be suppressed. In the case where the non-cross-linked resin particles and the adhesive are cross-linked by a cross-linking agent, the protrusion may contain only a cross-linked resin, or may contain a cross-linked resin and a non-cross-linked resin.

[0147] (additive)

[0148] The resin layer may contain additives other than the above-mentioned substances constituting the protrusions and the binder.

[0149] Examples of the additive contained in the resin layer include surfactants, waxes, dispersants, antioxidants, ultraviolet absorbers, colorants, reinforcing agents, plasticizers, antistatic agents, flame retardants, rust preventives, and mildew preventives.

[0150] From the viewpoint of improving the smoothness of the area other than the part where the protrusions are present on the second main surface, the resin layer preferably contains a surfactant. By improving the smoothness of the above-mentioned area of ​​the second main surface and reducing the surface roughness of the second main surface in factors other than the presence of the protrusions, the physical properties including the ratio of the height of the protrusions to the major diameter of the protrusions and the height of the protrusions can be controlled within a desired range, thereby further suppressing concavo-convex defects.

[0151] The surfactant is not particularly limited, and examples thereof include silicone surfactants, fluorine surfactants, and hydrocarbon surfactants. From the viewpoint of being able to suppress charge on the second main surface, hydrocarbon surfactants are preferred.

[0152] The silicone-based surfactant is not particularly limited as long as it has a silicon-containing group as a hydrophobic group, and examples thereof include polydimethylsiloxane, polyether-modified polydimethylsiloxane, and polymethylalkylsiloxane.

[0153] Examples of commercially available silicone surfactants include BYK (registered trademark)-306, BYK-307, BYK-333, BYK-341, BYK-345, BYK-346, BYK-347, BYK-348, and BYK-349 (all manufactured by BYK Co., Ltd.), and KF-351A, KF-352A, KF-353, KF-354L, KF-355A, KF-615A, KF-945, KF-640, KF-642, KF-643, KF-6020, X-22-4515, KF-6011, KF-6012, KF-6015, and KF-6017 (all manufactured by Shin-Etsu Chemical Co., Ltd.). Co., Ltd. manufacturing).

[0154] The fluorine-based surfactant is not particularly limited as long as it has a fluorine-containing group as a hydrophobic group, and examples thereof include perfluorooctanesulfonic acid and perfluorocarboxylic acid.

[0155] Commercially available products of fluorine-based surfactants include, for example, MEGAFACE (registered trademark) F-114, F-410, F-440, F-447, F-553, and F-556 (all manufactured by DIC Corporation), and Surflon (registered trademark) S-211, S-221, S-231, S-233, S-241, S-242, S-243, S-420, S-661, S-651, and S-386 (manufactured by AGC SEIMICHEMICAL CO., LTD.).

[0156] Furthermore, as the fluorine-based surfactant, from the viewpoint of improving environmental compatibility, a surfactant derived from an alternative material to a compound having a linear perfluoroalkyl group having 7 or more carbon atoms, such as perfluorooctanoic acid (PFOA) and perfluorooctane sulfonic acid (PFOS) is preferred.

[0157] Examples of the hydrocarbon-based surfactant include anionic surfactants, nonionic surfactants, cationic surfactants, and amphoteric surfactants.

[0158] Examples of the anionic surfactant include alkyl sulfates, alkyl sulfonates, alkylbenzene sulfonates, alkyl phosphates, and fatty acid salts.

[0159] Examples of the nonionic surfactant include polyalkylene glycol mono- or dialkyl ethers, polyalkylene glycol mono- or dialkyl esters, and polyalkylene glycol monoalkyl ester / monoalkyl ether.

[0160] Examples of the cationic surfactant include primary and tertiary alkylamine salts and quaternary ammonium compounds.

[0161] Examples of the amphoteric surfactant include a surfactant having both an anionic part and a cationic part in the molecule.

[0162] Examples of commercially available anionic surfactants include RAPISOL (registered trademark) A-90, A-80, BW-30, B-90, and C-70 (manufactured by NOF CORPORATION), NIKKOL (registered trademark) OTP-100 (manufactured by Nikko Chemicals Co., Ltd.), Kohacool (registered trademark) ON, L-40, and PHOSPHANOL (registered trademark) 702 (manufactured by TOHO Chemical Industry Co., Ltd.), and BEAULIGHT (registered trademark) A-5000 and SSS (manufactured by Sanyo Chemical Industries, Ltd.).

[0163] Examples of commercially available nonionic surfactants include NAROACTY (registered trademark) CL-95 and HN-100 (trade names, manufactured by Sanyo Chemical Industries, Ltd.), Risorex BW400 (trade name, manufactured by Kokyu Alcohol Kogyo Co., Ltd.), Emalex (registered trademark) ET-2020 (both manufactured by NIHON EMULSION Co., Ltd.), and SURFINOL (registered trademark) 104E, 420, 440, 465, and Dynol (registered trademark) 604, 607 (both manufactured by Nissin Chemical Industry Co., Ltd.).

[0164] As the hydrocarbon-based surfactant, from the viewpoint of being able to form a coating layer with a smooth surface without hindering the dispersion of the resin, at least one of anionic surfactants and nonionic surfactants is preferred, and anionic surfactants are more preferred. That is, from the viewpoint of improving surface smoothness, anionic hydrocarbon-based surfactants are more preferred as the surfactant.

[0165] From the viewpoint of further improving the smoothness, the anionic hydrocarbon-based surfactant preferably has a plurality of hydrophobic terminal groups. The hydrophobic terminal group may be a part of the hydrocarbon group possessed by the hydrocarbon-based surfactant. For example, a hydrocarbon-based surfactant having a hydrocarbon group containing a branched structure at the end has a plurality of hydrophobic terminal groups.

[0166] Examples of anionic hydrocarbon surfactants having a plurality of hydrophobic terminal groups include sodium di-2-ethylhexyl sulfosuccinate (having four hydrophobic terminal groups), sodium di-2-ethyloctyl sulfosuccinate (having four hydrophobic terminal groups), and branched alkylbenzene sulfonates (having two hydrophobic terminal groups).

[0167] The surfactant may be used alone or in combination of two or more.

[0168] The content of the surfactant is preferably 0.1 to 10% by mass, more preferably 0.1 to 5% by mass, and further preferably 0.5 to 2% by mass, based on the total mass of the resin layer, from the viewpoint of achieving better surface smoothness.

[0169] The wax is not particularly limited and may be a natural wax or a synthetic wax. Examples of natural wax include carnauba wax, candelilla wax, beeswax, montan wax, paraffin wax, and petroleum wax. In addition, the lubricant described in

[0087] of the specification of International Publication No. 2017 / 169844 may also be used.

[0170] The content of the wax is preferably 0 to 10% by mass relative to the total mass of the resin layer.

[0171] (thickness)

[0172] The resin layer can be formed, for example, by coating a composition containing particles on one surface of a resin substrate as described below. In this case, the thickness of the resin layer is often 0.001 to 1 μm, and from the viewpoint of suppressing the concavo-convex defects of the formed functional layer during long-term storage of a laminated film made using the present film, it is more preferably 0.01 to 1 μm, and further preferably 0.02 to 1 μm.

[0173] Furthermore, the resin layer may be formed by coextruding a resin for forming the resin substrate and a resin for forming the resin layer. In this case, the thickness of the resin layer is often 1 to 10 μm.

[0174] From the viewpoint of the production suitability of the resin layer and the reduction of haze, the thickness of the resin layer is preferably 10 to 500 nm, more preferably 20 to 250 nm, and even more preferably 20 to 100 nm.

[0175] A sample having a cross section perpendicular to the main surface of the film is prepared, and the thickness of the resin layer is measured using a scanning electron microscope (SEM) or a transmission electron microscope (TEM). More specifically, the thickness of any five locations of the resin layer of the sample where no protrusions are formed is measured, and the arithmetic average thereof is taken as the thickness of the resin layer.

[0176] The method for forming the resin layer will be described in detail in the “resin layer forming step” described later.

[0177] <Resin base material>

[0178] The resin substrate is a film-like object containing a resin as a main component. Here, the "main component" refers to the component with the largest content (mass) among all the components contained in the film-like object.

[0179] The resin contained as a main component in the resin substrate is not particularly limited, and a known resin can be used. Since the present film has a characteristic in the resin layer, it is possible to suppress uneven defects regardless of the type of the resin substrate.

[0180] As the resin contained in the resin substrate, for example, polyester resin, carbonate resin, fluororesin, polyimide resin, triacetyl cellulose resin, polyether resin, olefin resin, acrylic resin, styrene resin, vinyl chloride resin, vinyl alcohol resin and nylon resin can be cited. From the viewpoint of heat resistance and transparency, polyester resin, carbonate resin, fluororesin, polyimide resin, triacetyl cellulose resin, polyether resin or olefin resin is preferred, and from the viewpoint of moldability and versatility, polyester resin is more preferred.

[0181] The resin substrate is preferably a resin substrate containing the above-mentioned preferred resin as a main component. That is, the resin substrate is preferably a polyester substrate, a polycarbonate substrate, a fluororesin substrate, a polyimide substrate, a triacetylcellulose substrate, a polyether substrate or a polyolefin substrate, and more preferably a polyester substrate.

[0182] The resin substrate may contain two or more resins. For example, the polyester substrate may contain a single polyester resin or may contain two or more polyester resins.

[0183] The resin substrate is preferably a biaxially oriented resin substrate, and more preferably a biaxially oriented polyester substrate. That is, the present film is also preferably a biaxially oriented film.

[0184] "Biaxial orientation" refers to the property of having molecular orientation in two axial directions. Molecular orientation is measured using a microwave transmission type molecular orientation meter (e.g., MOA-6004, manufactured by Oji Scientific Instruments Co., Ltd.). The angle between the two axial directions is preferably within the range of 90°±5°, more preferably within the range of 90°±3°, and further preferably within the range of 90°±1°.

[0185] The molecular orientation changes by stretching, and a biaxially oriented resin substrate can be produced by biaxially stretching.

[0186] The resin substrate preferably does not substantially contain particles. "Substantially containing no particles" is defined as for the resin substrate, when the element derived from the particles is quantitatively analyzed by fluorescent X-ray analysis, the content of the particles relative to the total mass of the resin substrate is 50 mass ppm or less, preferably 10 mass ppm or less, and more preferably below the detection limit. This is because, even if the particles are not actively added to the resin substrate, the pollutant components derived from foreign matter, the raw resin or the dirt attached to the production line or device in the manufacturing process of the resin substrate will also be peeled off and mixed into the resin substrate. As particles, for example, the above-mentioned particles for forming a resin layer can be cited.

[0187] Hereinafter, the polyester resin contained in the polyester substrate and the polyester substrate will be mainly described, but as described above, the resin substrate of the present film is not limited to the polyester substrate.

[0188] (Polyester resin)

[0189] The polyester resin is a polymer having an ester bond in the main chain. The polyester resin is generally formed by polycondensing a dicarboxylic acid compound and a diol compound described below.

[0190] The polyester resin is not particularly limited, and known polyester resins can be used. Examples of the polyester resin include polyethylene terephthalate (PET), polypropylene terephthalate (PPT), polybutylene terephthalate (PBT), polyethylene 2,6-naphthalate (PEN), and copolymers thereof, preferably PET, PEN, and copolymers thereof, and more preferably PET.

[0191] The intrinsic viscosity of the polyester resin is preferably 0.50 dl / g or more and less than 0.80 dl / g, and more preferably 0.55 dl / g or more and less than 0.70 dl / g.

[0192] The melting point (Tm) of the polyester resin is preferably 220 to 270°C, more preferably 245 to 265°C.

[0193] The glass transition temperature (Tg) of the polyester resin is preferably 65 to 90°C, more preferably 70 to 85°C.

[0194] The method for producing the polyester resin is not particularly limited, and a known method can be used. For example, the polyester resin can be produced by polycondensing at least one dicarboxylic acid compound and at least one diol compound in the presence of a catalyst.

[0195] -catalyst-

[0196] The catalyst used in the production of the polyester resin is not particularly limited, and any known catalyst that can be used in the synthesis of the polyester resin can be used.

[0197] Examples of the catalyst include alkali metal compounds (e.g., potassium compounds, sodium compounds), alkaline earth metal compounds (e.g., calcium compounds, magnesium compounds), zinc compounds, lead compounds, manganese compounds, cobalt compounds, aluminum compounds, antimony compounds, titanium compounds, germanium compounds, and phosphorus compounds. Among them, titanium compounds are preferred from the viewpoint of catalytic activity and cost.

[0198] The catalyst may be used alone or in combination of two or more. It is preferred to use at least one metal catalyst selected from potassium compounds, sodium compounds, calcium compounds, magnesium compounds, zinc compounds, lead compounds, manganese compounds, cobalt compounds, aluminum compounds, antimony compounds, titanium compounds and germanium compounds and a phosphorus compound, and more preferably to use a titanium compound and a phosphorus compound in combination.

[0199] As the titanium compound, an organic chelate titanium complex is preferred. The organic chelate titanium complex is a titanium compound having an organic acid as a ligand.

[0200] Examples of the organic acid include citric acid, lactic acid, trimellitic acid, and malic acid.

[0201] As the titanium compound, the titanium compounds described in

[0049] to

[0053] of Japanese Patent No. 5575671 can also be used, and the contents of the above publication are incorporated into the present specification.

[0202] -Dicarboxylic acid compound-

[0203] Examples of the dicarboxylic acid compound include dicarboxylic acids such as aliphatic dicarboxylic acid compounds, alicyclic dicarboxylic acid compounds, and aromatic dicarboxylic acid compounds, and dicarboxylic acid esters such as methyl ester compounds and ethyl ester compounds of these dicarboxylic acids. Among them, aromatic dicarboxylic acids or aromatic dicarboxylic acid methyl esters are preferred.

[0204] Examples of the aliphatic dicarboxylic acid compound include malonic acid, succinic acid, glutaric acid, adipic acid, suberic acid, sebacic acid, dodecanedioic acid, dimer acid, eicosanedioic acid, pimelic acid, azelaic acid, methylmalonic acid, and ethylmalonic acid.

[0205] Examples of the alicyclic dicarboxylic acid compound include adamantane dicarboxylic acid, norbornene dicarboxylic acid, cyclohexane dicarboxylic acid, and decahydronaphthalene dicarboxylic acid.

[0206] Examples of the aromatic dicarboxylic acid compound include terephthalic acid, isophthalic acid, phthalic acid, 1,4-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 1,8-naphthalene dicarboxylic acid, 4,4'-diphenyl dicarboxylic acid, 4,4'-diphenyl ether dicarboxylic acid, sodium 5-sulfoisophthalate, phenylindan dicarboxylic acid, anthracene dicarboxylic acid, phenanthrene dicarboxylic acid and 9,9'-bis(4-carboxyphenyl)fluorene acid.

[0207] Among them, terephthalic acid or 2,6-naphthalene dicarboxylic acid is preferred, and terephthalic acid is more preferred.

[0208] The dicarboxylic acid compound may be used alone or in combination of two or more. When terephthalic acid is used as the dicarboxylic acid compound, terephthalic acid may be used alone or in a copolymer with other aromatic dicarboxylic acids such as isophthalic acid or aliphatic dicarboxylic acids.

[0209] -Diol compound-

[0210] Examples of the diol compound include aliphatic diol compounds, alicyclic diol compounds, and aromatic diol compounds, and aliphatic diol compounds are preferred.

[0211] Examples of the aliphatic diol compound include ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,2-butanediol, 1,3-butanediol, and neopentyl glycol, and ethylene glycol is preferred.

[0212] Examples of the alicyclic diol compound include cyclohexanedimethanol, spirodiol, and isosorbide.

[0213] Examples of the aromatic diol compound include bisphenol A, 1,3-benzenedimethanol, 1,4-benzenedimethanol, and 9,9′-bis(4-hydroxyphenyl)fluorene.

[0214] The diol compounds may be used alone or in combination of two or more.

[0215] -Capping agent-

[0216] In the production of the polyester resin, a terminal blocking agent may be used as necessary. By using the terminal blocking agent, a structure derived from the terminal blocking agent is introduced into the terminal of the polyester resin.

[0217] The terminal blocking agent is not limited, and a known terminal blocking agent can be used. Examples of the terminal blocking agent include oxazoline compounds, carbodiimide compounds, and epoxy compounds.

[0218] As the terminal blocking agent, the contents described in

[0055] to

[0064] of JP-A-2014-189002 can also be referred to, and the contents of the above publication are incorporated into the present specification.

[0219] - Manufacturing conditions -

[0220] The reaction temperature is not limited and may be appropriately set according to the raw materials. The reaction temperature is preferably 260 to 300°C, more preferably 275 to 285°C.

[0221] The pressure is not limited and can be set appropriately according to the raw materials. The pressure is preferably 1.33×10 -3 ~1.33×10 - 5 MPa, more preferably 6.67×10 -4 ~6.67×10 -5 MPa.

[0222] As a method for synthesizing the polyester resin, the method described in

[0033] to

[0070] of Japanese Patent No. 5575671 can also be used, and the contents of the above publication are incorporated into this specification.

[0223] The content of the polyester resin in the polyester substrate is preferably 85% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, and particularly preferably 98% by mass or more, based on the total mass of the polymer in the polyester substrate.

[0224] The upper limit of the content of the polyester resin is not limited, and can be appropriately set within the range of 100% by mass or less relative to the total mass of the polymer in the polyester substrate.

[0225] When the polyester substrate contains polyethylene terephthalate, the content of polyethylene terephthalate is preferably 90 to 100% by mass, more preferably 95 to 100% by mass, further preferably 98 to 100% by mass, and particularly preferably 100% by mass, based on the total mass of the polyester resin in the polyester substrate.

[0226] The resin substrate may contain components other than the resin (for example, a catalyst, unreacted raw material components, particles, water, etc.).

[0227] The thickness of the resin substrate is preferably 300 μm or less, more preferably 100 μm or less, further preferably 50 μm or less, and particularly preferably 40 μm or less. The lower limit of the thickness is not particularly limited, but from the viewpoint of improving strength and processability, it is preferably 3 μm or more, more preferably 10 μm or more, and further preferably 20 μm or more.

[0228] The thickness of the resin substrate is measured according to the method for measuring the thickness of a film described later.

[0229] The present film may further include layers other than the above-mentioned resin layer and resin substrate, but preferably has a layer structure consisting of a resin layer and a resin substrate.

[0230] 〔Physical properties, etc.〕

[0231] Next, the physical properties and the like of the present film will be described.

[0232] <Physical Properties of Resin Layer>

[0233] (Ratio of the protrusion height to the protrusion's major diameter)

[0234] In the present film, the resin layer has protrusions on the surface thereof, and the ratio of the height of the protrusions to the major diameter of the protrusions is 0.70 or less.

[0235] The ratio of the height of the protrusion to the major diameter of the protrusion is defined by a value measured as follows.

[0236] The surface of the resin layer (second main surface) was observed using a scanning electron microscope with an area of ​​10000 μm. 2The area of ​​the protrusion with the longest long diameter is selected in the above area. The ratio of the height of the selected protrusion measured by non-contact surface shape measurement using an optical interferometer to the long diameter of the selected protrusion measured using a scanning electron microscope is set as the ratio of the height of the protrusion to the long diameter of the protrusion.

[0237] The ratio of the height of the protrusion to the major diameter of the protrusion is 0.70 or less, preferably 0.60 or less, and more preferably 0.30 or less. Within the above range, unevenness defects can be further suppressed, and the windability is also excellent.

[0238] The lower limit is not particularly limited, but from the viewpoint of excellent transportability and the viewpoint of suppressing variation in protrusion height, the ratio of the protrusion height to the major axis of the protrusion is preferably 0.01 or more, more preferably 0.03 or more, and further preferably 0.05 or more.

[0239] The ratio of the height of the protrusions on the surface of the resin layer of the present film to the major diameter of the protrusions can be adjusted by, for example, the type and average particle size of the particles used to manufacture the resin layer, the thickness of the resin layer, and the heat treatment during and after the resin layer forming step described later. The method for manufacturing the film that can more easily perform the above adjustment will be described in detail in the following section.

[0240] The ratio of the height of the protrusions on the surface of the resin layer of the present film to the major diameter of the protrusions is measured by the method described in the Examples section described later.

[0241] In addition, dust and foreign matter present on the film surface, dirt attached from a production line or an apparatus during the manufacturing process of the resin substrate, and the like are not included in the protrusions on the surface of the resin layer.

[0242] (Protrusion height, protrusion major diameter, protrusion minor diameter on the resin layer surface)

[0243] The resin layer of the present film functions as a transport surface in the present film or in a laminated film obtained by forming a functional layer on the first main surface. From the viewpoint of excellent transportability, the height of the protrusions on the surface of the resin layer of the present film is preferably 0.1 μm or more, more preferably 0.2 μm or more, further preferably 0.25 μm or more, particularly preferably 0.3 μm or more, and most preferably 0.33 μm or more.

[0244] On the other hand, if the protrusions on the surface of the resin layer are too large, the substances constituting the protrusions are easy to fall off during transportation. In addition, transfer marks may sometimes be formed on the functional layer when the roll of the laminated film is stored. From these viewpoints, the height of the protrusions on the surface of the resin layer is preferably 5 μm or less, more preferably 4.0 μm or less, and further preferably 3.5 μm or less. From the viewpoint of winding properties, the lower limit is preferably 0.1 μm or more, and more preferably 0.3 μm or more.

[0245] That is, from the viewpoint of further suppressing uneven defects and excellent transport properties, the height of the protrusions on the surface of the resin layer is preferably within the range defined by the lower limit and upper limit described above.

[0246] In this specification, the term "height of protrusions on the surface of the resin layer" refers to the height of the protrusions on the surface of the resin layer (second main surface) observed using a scanning electron microscope over an area of ​​10,000 μm. 2 The protrusion height is obtained by measuring the non-contact surface shape of the protrusion with the longest major axis in the above area using an optical interferometer.

[0247] From the viewpoint of excellent transportability and further suppression of uneven defects, the protrusion height on the second main surface is preferably 0.3 to 5.0 μm, and the thickness of the resin layer is preferably 10 to 500 nm (more preferably 20 to 100 nm).

[0248] The major diameter of the protrusions on the surface of the resin layer of the present film is preferably 0.1 to 20 μm, more preferably 0.5 to 10 μm, and further preferably 1 to 8 μm.

[0249] The minor diameter of the protrusions on the surface of the resin layer of the present film is preferably 0.1 to 20 μm, more preferably 0.3 to 10 μm, and further preferably 1 to 8 μm.

[0250] The ratio of the major axis of the protrusion to the minor axis of the protrusion is preferably 1.0 or more, more preferably 1.2 or more, further preferably 1.6 or more, and particularly preferably more than 1.6. The upper limit of the ratio of the major axis of the protrusion to the minor axis of the protrusion is 5.0.

[0251] The major diameter and minor diameter of the protrusions on the surface of the resin layer can be adjusted by the method of adjusting the ratio of the height of the protrusions to the major diameter of the protrusions described above.

[0252] The major axis and minor axis of the protrusions on the surface of the resin layer were measured by the method described in the Examples section described later.

[0253] (Number of protrusions)

[0254] On the surface of the resin layer of the present film, the number of protrusions per 10000 μm of observation area is 2 The number of protrusions is preferably 50 or more, more preferably 80 or more, and further preferably 200 or more. The number of protrusions is preferably 20,000 or less, more preferably 15,000 or less, and further preferably 13,000 or less.

[0255] In this specification, the term "number of protrusions" refers to the number of protrusions per 10,000 μm2 of the surface (second main surface) of the resin layer observed using a scanning electron microscope. 2 The total number of protrusions in the observation area that are considered to be protrusions.

[0256] Here, in the measurement method described in the Examples section below, protrusions having a major diameter of 0.01 μm or more can be regarded as protrusions.

[0257] (Surface average roughness Sa of resin layer surface)

[0258] From the viewpoint of further suppressing uneven defects, the surface average roughness Sa of the resin layer surface is preferably 1 to 15 nm, more preferably 1 to 10 nm, and further preferably 1 to 8 nm.

[0259] The surface average roughness Sa of the resin layer surface can be adjusted by, for example, selecting the average particle size and content of particles used to manufacture the resin layer, the thickness of the resin layer, and the types of non-polyester resins and additives (surfactants, etc.) that can be included in the resin layer. When the resin layer is formed by in-line coating, the above adjustment can be performed more easily.

[0260] The surface average roughness Sa of the resin layer surface is determined by measuring the surface of the resin layer side of the film under the same conditions as the conditions for measuring the protrusion height when the ratio of the protrusion height to the major diameter of the protrusion is obtained using an optical interferometer (e.g., "Vertscan 3300G Lite" manufactured by Hitachi High-Tech Corporation, etc.), and then analyzing using built-in data analysis software. In the measurement of the surface average roughness Sa, the measurement position is changed and the measurement is performed 5 times, and the average value of the obtained measurement values ​​is taken as the measurement value of the surface average roughness Sa.

[0261] (Surface free energy of resin layer surface)

[0262] The surface free energy of the second main surface of the film is preferably 25 to 65 mJ / m from the viewpoint of improving the windability during transportation and from the viewpoint of excellent effect of suppressing uneven defects during long-term storage. 2 , more preferably 25 to 56 mJ / m 2 , more preferably 25 to 45 mJ / m 2 , especially preferably 35 to 45 mJ / m 2 By keeping the surface free energy of the resin layer surface within the above range, it is possible to suppress impurities such as oligomers generated from the resin substrate from passing through the resin layer and precipitating on the surface of the resin layer. As a result, when the laminated film manufactured using the present film is rolled up and stored for a long time, particles derived from impurities such as oligomers generated on the conveying surface (the second main surface) can be suppressed from adhering to the surface of the functional layer of the laminated film and becoming the cause of uneven defects.

[0263] The surface free energy of the resin layer surface can be adjusted by, for example, selecting the non-polyester resin and additives contained in the resin layer.

[0264] The surface free energy of the resin layer surface of the present film can be determined by the method described in the Examples section described later.

[0265] <Physical Properties of First Main Surface>

[0266] (Maximum protrusion height Sp and surface average roughness Sa of the first main surface)

[0267] From the viewpoint of making the functional layer smooth, the first main surface is preferably as smooth as possible. Specifically, the maximum protrusion height Sp of the first main surface is preferably 1 to 60 nm, more preferably 1 to 50 nm, and further preferably 1 to 30 nm.

[0268] The surface average roughness Sa of the first main surface is preferably 0 to 10 nm, more preferably 0 to 5 nm, and further preferably 0 to 2 nm.

[0269] The maximum protrusion height Sp and the surface average roughness Sa of the first main surface can be adjusted by, for example, substantially not including particles in the resin base material and selecting the type of resin constituting the resin base material and the type of additives so as to form a smooth film.

[0270] The maximum protrusion height Sp and the surface average roughness Sa of the first main surface of the present film are measured on the first main surface under the same conditions as the conditions for measuring the protrusion height when the ratio of the protrusion height to the major diameter of the protrusion is obtained using an optical interferometer (e.g., "Vertscan 3300G Lite" manufactured by Hitachi High-Tech Corporation, etc.), and then analyzed using built-in data analysis software. In the measurement of the maximum protrusion height Sp and the surface average roughness Sa, the measurement position is changed on the first main surface and the measurement is performed 5 times, and the average value of the obtained measurement values ​​is used as each measurement value.

[0271] (Surface free energy of the first main surface)

[0272] From the viewpoint of antistatic when the film is wound up, the surface free energy of the first main surface of the film is preferably 25 to 65 mJ / m 2 , more preferably 30 to 45 mJ / m 2 .

[0273] The surface free energy of the first main surface can be adjusted by selecting the type of resin forming the resin base material, additives, and the like.

[0274] The surface free energy of the first main surface of the present film can be measured according to the above-mentioned method for measuring the surface free energy of the second main surface.

[0275] <Thickness>

[0276] The thickness of the film is preferably 100 μm or less, more preferably 50 μm or less, and further preferably 40 μm or less. The lower limit of the thickness is not particularly limited, but is preferably 3 μm or more, more preferably 5 μm or more, and further preferably 10 μm or more from the viewpoint of excellent handleability.

[0277] The thickness of the film was determined as the arithmetic mean of the thicknesses at five locations measured using a stylus film thickness meter. In the above measurement, the measurement was performed at five different locations in the same direction.

[0278] [Method for producing film]

[0279] Examples of a method for producing the present film include a method including a stretching step of stretching a resin substrate and a step of forming a resin layer having protrusions.

[0280] The stretching performed in the stretching step may be uniaxial stretching or biaxial stretching, but biaxial stretching is preferred. That is, the obtained film is preferably a biaxially oriented film.

[0281] As a method for producing the film of the present invention, for example, the following aspects can be mentioned.

[0282] The method comprises the following steps: forming a layer on at least one surface of a resin substrate using a composition comprising non-crosslinked resin particles A, resin B and a solvent; and

[0283] The method for producing the film comprises the step of stretching the resin substrate having the layer formed thereon while heating it at a temperature Y, and satisfies requirements 1 and 2 described later.

[0284] According to the above manufacturing method, the present film can be obtained. That is, the present film can be obtained, which at least comprises a resin substrate and a resin layer, wherein the resin layer has protrusions on its surface, and the ratio of the height of the protrusions to the major diameter of the protrusions is 0.70 or less. In other words, according to the above manufacturing method, it is easy to adjust the ratio of the height of the protrusions on the surface of the resin layer of the present film to the major diameter of the protrusions to 0.70 or less.

[0285] Hereinafter, the present film in which the stretching step is a biaxial stretching step and a biaxially oriented film is obtained will be described representatively. That is, the resin substrate will be described as a stretched resin substrate, but the present film production method is not limited to the following. In addition, the preferred mode of the steps in the above-mentioned production method is the same as the preferred mode of the following mode.

[0286] [Method for producing biaxially oriented film]

[0287] Examples of a method for producing the film of the present invention include a method comprising a biaxial stretching step of biaxially stretching an unstretched resin substrate and a step of forming a resin layer having protrusions.

[0288] The biaxial stretching may be simultaneous biaxial stretching in which longitudinal stretching and transverse stretching are performed simultaneously, or may be sequential biaxial stretching in which longitudinal stretching and transverse stretching are performed in multiple stages of two or more stages. As the order of sequential biaxial stretching, for example, the order of longitudinal stretching and transverse stretching, the order of longitudinal stretching, transverse stretching and longitudinal stretching, the order of longitudinal stretching, longitudinal stretching and transverse stretching, and the order of transverse stretching and longitudinal stretching can be cited, and the order of longitudinal stretching and transverse stretching is preferred.

[0289] Hereinafter, a first embodiment will be described as an example of the method for producing the present film.

[0290] [First embodiment]

[0291] The first embodiment of the method for producing the film includes the following steps:

[0292] A step of stretching an unstretched resin substrate to obtain a uniaxially stretched resin substrate (hereinafter also referred to as a "longitudinal stretching step");

[0293] A step of forming a layer on at least one surface of the uniaxially stretched resin substrate using a composition containing non-crosslinked resin particles A, resin B, and a solvent (hereinafter also referred to as a "layer forming step"); and

[0294] The process of stretching the uniaxially stretched resin substrate having the above-mentioned layer formed thereon while heating it at a temperature Y (hereinafter also referred to as a "transverse stretching process") satisfies the following requirements 1 and 2 in the method for producing the film.

[0295] Requirement 1: The value obtained by subtracting the glass transition temperature of the non-crosslinked resin particles A from the temperature Y is -20 to 50°C.

[0296] Requirement 2: When the resin B is present in the composition in the form of particles, the particle size of the resin B in the form of particles is smaller than the particle size of the non-crosslinked resin particles A.

[0297] According to the above manufacturing method, the present film of a biaxially oriented film can be obtained. That is, the present film can be obtained, which comprises at least a biaxially oriented resin substrate and a resin layer, wherein the resin layer has protrusions on its surface, and the ratio of the height of the protrusions to the major diameter of the protrusions is 0.70 or less. In other words, according to the above manufacturing method, it is easy to adjust the ratio of the height of the protrusions on the surface of the resin layer of the present film to the major diameter of the protrusions to 0.70 or less.

[0298] Hereinafter, each step will be described in detail.

[0299] <Longitudinal Stretching Process>

[0300] As the resin substrate to be subjected to the longitudinal stretching step, an unstretched resin substrate is preferred.

[0301] The resin substrate used in the longitudinal stretching step is as described in the above section <Resin substrate> including preferred embodiments. The unstretched resin substrate can be produced by, for example, the extrusion molding step described later.

[0302] The longitudinal stretching can be performed, for example, by conveying the unstretched resin substrate in the longitudinal direction while applying tension between two or more pairs of stretching rollers provided in the conveying direction.

[0303] The stretching ratio in the longitudinal stretching step can be appropriately set depending on the intended use, but is preferably 2.0 to 5.0 times, more preferably 2.5 to 4.0 times, and further preferably 2.8 to 4.0 times.

[0304] The stretching speed in the longitudinal stretching step is preferably 800 to 1500% / second, more preferably 1000 to 1400% / second, and further preferably 1200 to 1400% / second. Here, the "stretching speed" refers to the value expressed as a percentage of the value obtained by dividing the length Δd in the conveying direction of the resin substrate stretched in 1 second in the longitudinal stretching step by the length d0 in the conveying direction of the resin substrate before stretching.

[0305] In the longitudinal stretching process, it is preferred to heat the unstretched resin substrate. This is because longitudinal stretching is easy by heating. The heating temperature in the longitudinal stretching process can be appropriately set according to the type of resin constituting the resin substrate. For example, in the case of a polyester substrate, it is preferably 70 to 120°C, more preferably 80 to 110°C, and further preferably 85 to 100°C.

[0306] Here, the "temperature" in each process of the manufacturing method involved in this embodiment refers to the surface temperature of the film-like member measured using a non-contact thermometer (for example, a radiation thermometer). The surface temperature of the film-like member is obtained by measuring the temperature of the central part of the width direction of the film-like member five times and calculating the average value of the obtained measured values.

[0307] <Layer Formation Step>

[0308] In the layer forming step, a layer is formed on the surface of the uniaxially stretched resin substrate obtained in the longitudinal stretching step using a composition containing non-crosslinked resin particles A, resin B and a solvent (hereinafter also referred to as "composition A1").

[0309] At this time, when the resin B contained in the composition A1 is present in the form of particles, the above-mentioned requirement 2 is satisfied with respect to the non-crosslinked resin particles A and the resin B. That is, when the resin B is present in the form of particles in the composition A1, the particle size of the particle-shaped resin B is smaller than the particle size of the non-crosslinked resin particles A. By satisfying the above-mentioned requirement 2, on the surface of the layer formed in the present embodiment, it is easy to adjust the ratio of the height of the protrusions on the surface of the resin layer of the present film to the major diameter of the protrusions within the above-mentioned range.

[0310] Furthermore, when the resin B is in the form of particles, when the particle size of the resin B is Db μm and the particle size of the non-crosslinked resin particles A is Da, it is also preferable that the relationship of the following formula (1) is satisfied.

[0311] Formula (1) 7×Db <Da

[0312] Furthermore, it is also preferable that Da and Db satisfy the relationship of the following formula (2).

[0313] Formula (2) Da < 50 × Db

[0314] Regarding Da and Db, it is also preferred that the relationship of formula (1) and formula (2) is satisfied at the same time. When at least one of the above formulas (1) and (2) is satisfied, on the surface of the layer formed in this embodiment, it is easy to adjust the ratio of the height of the protrusion on the surface of the resin layer of the present film to the major diameter of the protrusion within the above range.

[0315] When composition A1 contains a plurality of types of non-crosslinked resin particles A and resin B, each combination of non-crosslinked resin particles A and resin B preferably satisfies at least one of the above formula (1) and formula (2).

[0316] The layer formed in the layer forming step has the same meaning as the layer described in detail in the above section <Resin layer>, except that it is specified as a resin layer including protrusions formed of organic particles.

[0317] As the layer forming step, for example, there can be mentioned a method of forming a coating film on the surface of a uniaxially stretched resin substrate stretched in the longitudinal direction using the composition A1 and drying the film as necessary.

[0318] First, a method for forming a layer using composition A1 will be described.

[0319] The composition A1 can be prepared by, for example, mixing the non-crosslinked resin particles A, the resin B, a solvent, and additives added as needed.

[0320] The non-crosslinked resin particles A are preferably selected from the non-crosslinked resin particles described in the above section <Resin layer>. Among them, the non-crosslinked resin particles A preferably have a glass transition temperature of 70 to 140°C.

[0321] Resin B is preferably selected from the non-polyester resins included as the binder described in the above section <Resin layer>. Among them, resin B is preferably a resin having an acid group. In addition, resin B preferably has a glass transition temperature of -50 to 105°C.

[0322] The glass transition temperature of the non-crosslinked resin particles A and the resin B can be determined by differential scanning calorimetry, and the detailed measurement method is described in the Examples section of the latter section. In addition, when commercial products are used as the non-crosslinked resin particles A and the resin B, the glass transition temperature recorded as the catalog value of the commercial product can be used.

[0323] The average particle size of the non-crosslinked resin particles A contained in the composition A1 is not particularly limited, but is preferably 1 nm to 3 μm, more preferably 10 nm to 2 μm, from the viewpoint of better conveyability and suppression of transfer marks.

[0324] When there is a catalog value from a manufacturer or the like, the average particle size of the non-crosslinked resin particles A can adopt the catalog value.

[0325] The non-crosslinked resin particles A contained in the composition A1 may be used alone or in combination of two or more.

[0326] When composition A1 contains two or more non-cross-linked resin particles A with different particle sizes, the formed layer preferably contains at least one non-cross-linked resin particle A with an average particle size within the above range, and more preferably, the two or more non-cross-linked resin particles A with different particle sizes are both non-cross-linked resin particles A with an average particle size within the above range.

[0327] The shape of the non-crosslinked resin particles A is not particularly limited, and examples thereof include rice grains, spheres, cubes, spindles, scales, aggregates, and irregular shapes. The aggregates refer to a state in which primary particles are aggregated.

[0328] From the viewpoint of transportability and coating properties, the content of the non-crosslinked resin particles A in composition A1 is preferably 0.1 to 30% by mass, more preferably 1 to 25% by mass, and further preferably 1 to 20% by mass, relative to the total mass of the components (solid content) excluding the solvent of composition A1.

[0329] Examples of the solvent include water and ethanol.

[0330] Composition A1 may contain a single solvent or two or more solvents.

[0331] The content of the solvent is preferably 80 to 99.5% by mass, more preferably 90 to 99.0% by mass, based on the total mass of Composition A1.

[0332] That is, in composition A1, the total content of the solid components is preferably 0.5 to 20% by mass, more preferably 1 to 10% by mass, relative to the total mass of composition A1.

[0333] The materials constituting the non-crosslinked resin particles A contained in the composition A1, the resin B (binder), and the additives, including their preferred embodiments, are as described in detail in the above section <Resin layer>.

[0334] Regarding the components in composition A1 other than the solvent and the non-crosslinked resin particles A, the content of each component in the coating liquid is preferably adjusted so that the content of each component relative to the total mass of the solid content of composition A1 is the same as the preferred content of each component relative to the total mass of the above-mentioned resin layer.

[0335] The composition A1 may contain a crosslinking agent, and the composition A1 preferably contains a crosslinking agent.

[0336] The cross-linking agent is not particularly limited, and a known cross-linking agent can be used.

[0337] As a cross-linking agent, for example, melamine compounds, oxazoline compounds, epoxy compounds, isocyanate compounds and carbodiimide compounds can be cited, preferably oxazoline compounds or carbodiimide compounds. As a commercial product, for example, CARBODILITE V-02-L2 (Nisshinbo Co., Ltd. manufacturing) and EPOCROS K-2020E (NIPPON SHOKUBAI CO., LTD. manufacturing) can be cited. For details of epoxy compounds, isocyanate compounds and melamine compounds, reference can be made to the records of

[0081] to

[0083] of Japanese Patent Publication No. 2015-163457. It is also possible to preferably use the cross-linking agent described in

[0082] to

[0084] of the International Publication No. 2017 / 169844 specification. As the carbodiimide compound, reference can be made to the descriptions of

[0038] to

[0040] of JP-A-2017-087421.

[0338] Regarding oxazoline compounds, carbodiimide compounds, and isocyanate compounds, cross-linking agents described in

[0074] to

[0075] of the specification of International Publication No. 2018 / 034294 can also be preferably used.

[0339] The content of the cross-linking agent is preferably 0 to 50% by mass relative to the total mass of the solid content of Composition A1.

[0340] The coating method of composition A1 is not particularly limited, and a known method can be used. Examples of the coating method include spray coating, slit coating, roll coating, knife coating, spin coating, bar coating, and dip coating.

[0341] In the layer forming step, it is preferred to apply an in-line coating method in which the composition A1 is applied to one surface of the uniaxially stretched resin substrate while the uniaxially stretched resin substrate is conveyed. By applying the in-line coating method, the heating time of the resin substrate in the manufacturing process is shortened and no thermal history is applied, thereby suppressing the generation of strain in the manufactured film and laminated film.

[0342] Furthermore, in this embodiment, after the longitudinal stretching step, the layer forming step is performed, followed by the transverse stretching step, thereby simultaneously stretching the uniaxially stretched resin substrate and the formed layer transversely, thereby improving the adhesion between the resin substrate and the formed resin layer.

[0343] <Horizontal Stretching Process>

[0344] In this embodiment, when performing a transverse stretching step of stretching the uniaxially stretched resin substrate having the above-mentioned layer in the width direction (hereinafter also referred to as "transverse stretching"), the transverse stretching step is performed while heating the uniaxially stretched resin substrate at a specific temperature Y.

[0345] The temperature Y at this time satisfies the above-mentioned requirement 1 with the glass transition temperature of the non-crosslinked resin particles A contained in the composition A1. That is, the value obtained by subtracting the glass transition temperature of the non-crosslinked resin particles A from the temperature Y is -20 to 50°C. By satisfying the above-mentioned requirement 1, the non-crosslinked resin particles A are easily deformed in the transverse stretching direction during transverse stretching, and on the surface of the resin layer formed in this embodiment, it is easy to adjust the ratio of the height of the protrusions to the major diameter of the protrusions within the above-mentioned range.

[0346] Furthermore, the uniaxially stretched resin substrate is preferably continuously heated at a temperature Y during the transverse stretching in the transverse stretching step. The temperature Y refers to the surface temperature of the uniaxially stretched resin substrate.

[0347] In the transverse stretching process, the uniaxially stretched resin substrate is preferably preheated before transverse stretching. The temperature of the uniaxially stretched resin substrate is increased by preheating, thereby making it easy to transversely stretch the uniaxially stretched resin substrate. The residual heat temperature in the transverse stretching process can be appropriately set according to the type of resin constituting the resin substrate. For example, in the case of a polyester substrate, it is preferably 80 to 120°C, and more preferably 90 to 110°C.

[0348] The stretching ratio in the width direction of the uniaxially stretched resin substrate in the transverse stretching step (transverse stretching ratio) is not particularly limited, but is preferably greater than the stretching ratio in the longitudinal stretching step. The stretching ratio in the transverse stretching step is preferably 3.0 to 6.0 times, more preferably 3.5 to 5.0 times, and further preferably 3.5 to 4.5 times.

[0349] When the transverse stretching step is performed in the stretching section of the stretching machine, the transverse stretching ratio is determined from the ratio (L1 / L0) of the width L1 of the resin substrate when it is taken out of the stretching section to the width L0 of the resin substrate when it is taken into the stretching section.

[0350] The stretching speed in the transverse stretching step is preferably 8 to 45% / sec, more preferably 10 to 30% / sec, and further preferably 15 to 20% / sec.

[0351] The production method according to the present embodiment may include other steps in addition to the longitudinal stretching step, the layer forming step, and the transverse stretching step.

[0352] The manufacturing method involved in this embodiment may, for example, include at least one process selected from the following processes: an extrusion molding process of extruding a molten resin containing a raw material resin into a film to form an unstretched resin substrate; a heat setting process of heating and heat-setting the biaxially stretched resin substrate; a heat relaxation process of heating the resin substrate that has been heat-set in the heat setting process at a temperature lower than that in the heat setting process to heat relax the resin substrate; a cooling process of cooling the resin substrate that has been heat-relaxed in the heat relaxation process; and an expansion process of expanding the heat-relaxed resin substrate in the width direction during the cooling process.

[0353] Hereinafter, each step will be described.

[0354] <Extrusion molding process>

[0355] The extrusion molding step is a step of extruding a molten resin including a raw material resin into a film by an extrusion molding method to form an unstretched resin substrate. The raw material resin has the same meaning as the resin described in the above item <Resin substrate>, and is preferably a polyester resin.

[0356] The extrusion molding method is a method of molding a raw material resin into a desired shape by, for example, extruding a melt of the raw material resin using an extruder.

[0357] By cooling, the melt extruded from the extrusion die is formed into a film. For example, by contacting the melt with a casting roll and cooling and solidifying the melt on the casting roll, the melt can be formed into a film. During the cooling of the melt, it is preferred that air (preferably cold air) is further blown to the melt.

[0358] <Heat setting process>

[0359] In the production method according to the present embodiment, it is preferable to perform a heat setting step as the heat treatment of the resin substrate that has been transversely stretched in the transverse stretching step.

[0360] In the heat setting step, the biaxially oriented resin substrate obtained in the transverse stretching step can be heated to be heat set. The resin is crystallized by heat setting, and shrinkage of the resin substrate can be suppressed.

[0361] The surface temperature of the resin substrate in the heat setting process (heat setting temperature) is not particularly limited and can be appropriately selected according to the type of resin, but is preferably less than 240° C., more preferably 235° C. or less, and further preferably 230° C. or less. The lower limit is not particularly limited, but is preferably 190° C. or more, more preferably 200° C. or more, and further preferably 210° C. or more. When the resin substrate is a polyester substrate, it is preferably within the above temperature range.

[0362] The heating time in the heat setting step is preferably 5 to 50 seconds, more preferably 5 to 30 seconds, and even more preferably 5 to 10 seconds.

[0363] <Heat relaxation process>

[0364] In the heat relaxation step, the resin base material heat-set in the heat setting step is preferably heated at a lower temperature than that in the heat setting step to perform heat relaxation. The heat relaxation can relax the residual strain of the resin base material.

[0365] The surface temperature of the resin substrate in the heat relaxation step (heat relaxation temperature) is preferably 5° C. or more lower than the heat setting temperature, more preferably 15° C. or more lower, further preferably 25° C. or more lower, and particularly preferably 30° C. or more lower. That is, the heat relaxation temperature is preferably 235° C. or less, more preferably 225° C. or less, further preferably 210° C. or less, and particularly preferably 200° C. or less.

[0366] The lower limit of the heat relaxation temperature is preferably 100°C or higher, more preferably 110°C or higher, and further preferably 120°C or higher.

[0367] <Cooling process>

[0368] The production method according to the present embodiment preferably includes a cooling step of cooling the thermally relaxed resin base material.

[0369] The cooling rate of the resin substrate in the cooling process is not particularly limited, but in order to reduce thermal shrinkage and impart dimensional stability, the cooling rate of the resin substrate in the cooling process is preferably greater than 500°C / min and less than 4000°C / min, more preferably 700 to 3000°C / min, and particularly preferably 1000 to 2500°C / min.

[0370] <Extended Process>

[0371] It is also preferable to include a step of expanding the heat-relaxed resin base material in the width direction in the cooling step.

[0372] The expansion rate of the resin substrate in the width direction in the expansion step, that is, the ratio of the width of the resin substrate at the end of the cooling step to the width of the resin substrate before the cooling step, is preferably 0% or more, more preferably 0.001% or more, and further preferably 0.01% or more.

[0373] The upper limit of the expansion rate is not particularly limited, but is preferably 1.3% or less, more preferably 1.2% or less, and further preferably 1.0% or less.

[0374] The production method according to the present embodiment may include a winding step of winding the biaxially oriented resin substrate obtained through the above steps to obtain a rolled biaxially oriented resin substrate.

[0375] The conveying speed of the resin substrate in each step except the longitudinal stretching step of the production method according to the present embodiment is not particularly limited, but is preferably 50 to 200 m / min, more preferably 80 to 150 m / min, from the viewpoint of productivity and quality.

[0376] The method for manufacturing the present film is not particularly limited as long as it is a method for manufacturing a film having a resin layer and a resin substrate, wherein the resin layer has protrusions on its surface, and the ratio of the height of the protrusions to the major axis of the protrusions is less than 0.70, and may also be a manufacturing method other than the above-mentioned first embodiment.

[0377] For example, the present film can be manufactured by co-extruding a molten resin containing a raw material resin for forming an unstretched resin substrate and a particle-containing molten resin containing particles and a resin (preferably a non-polyester resin) for forming a resin layer to form a laminated body in which an unstretched resin substrate and a resin layer are laminated, and then stretching (preferably biaxially stretching) the laminated body.

[0378] In the method for producing the present film, reference can be made to the contents of

[0113] to

[0169] of the specification of International Publication No. 2020 / 241692, and the contents are incorporated into the specification of the present application.

[0379] Furthermore, in the method for producing the present film specifically described above, a combination of two or more preferred aspects is a more preferred aspect.

[0380] [Laminated film]

[0381] The laminated film of the present invention is a laminated film comprising the present film and a functional layer, which comprises a resin layer including protrusions, a resin substrate and a functional layer in this order. That is, the functional layer is provided on the surface (first main surface) of the resin substrate of the present film on the side opposite to the resin layer side.

[0382] Since the functional layer is arranged on one surface of the film while the film is conveyed, and the obtained film is wound up, it is difficult for uneven defects to occur on the surface of the functional layer when it is then unwound, the laminated film of the present invention is difficult to produce uneven defects on the functional layer.

[0383] The type of the functional layer is not particularly limited, and examples thereof include a decorative layer, a photosensitive resin layer, a magnetic layer, a peeling layer, an adhesive layer, a conductive layer, a refractive index adjustment layer, a hard coating layer, and a visibility layer, and preferably one selected from the group consisting of a decorative layer, a photosensitive resin layer, and a peeling layer. In addition, it is also preferred that the laminated film is for optical use. As the functional layer for an optical laminated film, a decorative layer, a photosensitive resin layer, an adhesive layer, a refractive index adjustment layer, a hard coating layer, and a visibility layer can be mentioned.

[0384] More specific examples of laminated films include: a decorative film whose functional layer is a decorative layer; a photosensitive transfer film whose functional layer is a photosensitive resin layer and is used as a support for a dry film resist; a stripping film whose functional layer is a stripping layer (for example, a protective film for a dry film resist, a stripping film for manufacturing a ceramic green sheet, a stripping film for manufacturing a semiconductor process, a stripping film for a process); an adhesive film whose functional layer is an adhesive layer (for example, an adhesive film for manufacturing a semiconductor process); a film for a transparent conductive substrate whose functional layer is a transparent conductive layer; a transfer film whose functional layer is an inorganic layer (for example, a hard coating film whose inorganic layer is a hard coating layer, a base film whose inorganic layer is a magnetic layer or a ceramic green sheet); a photosensitive transfer film for forming an etching resist film whose functional layer is a photosensitive resin layer and a visible layer; and a photosensitive transfer film for forming a protective film for a touch panel whose functional layer is a photosensitive resin layer and a refractive index adjustment layer.

[0385] The method of stacking the functional layer on the surface of the present film is not particularly limited. It is preferred to apply a coating liquid containing the material constituting the functional layer to the surface (first main surface) of the present film to form the functional layer. From the viewpoint of better productivity, it is more preferred to form the functional layer by coating the functional layer coating liquid on the surface of the present film while conveying the present film and then heating the coating film.

[0386] The laminated film may have layers other than the present film and the functional layer. Examples of the layers other than the present film and the functional layer include a base layer containing a binder resin provided for the purpose of improving the adhesion between the present film and the functional layer.

[0387] When a decorative layer is laminated on the present film as a functional layer, the decorative layer preferably contains a colorant and an adhesive. When the decorative layer is used to form a decorative pattern, the decorative layer is preferably a colored photosensitive resin layer. As a colored photosensitive resin layer, a photosensitive resin layer formed of a photosensitive resin composition described in the specification of International Publication No. 2017 / 208849 is preferred. The colored photosensitive resin layer is preferably a layer having a pigment as a colorant, and more preferably a layer having, for example, a pigment, an adhesive polymer, a multifunctional acrylate, and a photopolymerization initiator.

[0388] As pigments, inorganic pigments (including pigments containing metal particles such as silver, etc.) and organic pigments can be preferably cited. The decorative film (laminated film) formed by laminating the present film and the decorative layer can suppress concave-convex defects, and can therefore be preferably used in fields requiring suppression of color unevenness.

[0389] When a photosensitive resin layer is laminated on the present film as a functional layer, a photosensitive resin layer containing a photosensitive resin may be provided, and a decorative layer, a refractive index adjusting layer and / or a visibility layer may be laminated.

[0390] The photosensitive resin layer is not particularly limited, but is preferably a negative type. Specifically, as a preferred embodiment, the binder polymer, ethylenically unsaturated compound or photopolymerization initiator described in the specification of International Publication No. 2018 / 105313 can be cited. The photosensitive resin layer is more preferably a layer having an alkali-soluble acrylic resin containing a cyclic structure, a multifunctional acrylate, an oxime-based photopolymerization initiator or a biimidazole-type photopolymerization initiator.

[0391] When the photosensitive resin layer is a dry film resist for forming an electrode protective film for a touch panel, it is preferred that a refractive index adjustment layer is laminated separately with the photosensitive resin layer. As a preferred embodiment of the refractive index adjustment layer, the second curable transparent resin layer described in Japanese Patent Application Publication No. 2014-108541 can be cited. The refractive index of the refractive index adjustment layer is preferably 1.6 or more, and the refractive index adjustment layer preferably has metal oxide particles with high refractive index such as titanium oxide and zirconium oxide.

[0392] When the photosensitive resin layer is a dry film resist for forming an etching resist used in forming a fine pattern of 50 μm or less, it is preferred that a visibility layer be laminated separately from the photosensitive resin layer. The visibility layer enables visual recognition in the step of confirming the pattern latent image.

[0393] When a release layer is laminated on the present film as a functional layer, the release layer contains at least a resin as a release agent.

[0394] The resin contained in the release layer is not particularly limited, and examples thereof include silicone resins, fluororesins, alkyd resins, acrylic resins, various waxes, and aliphatic olefins. When the release film is a release film for producing a ceramic green sheet described later, silicone resin is preferred from the viewpoint of the releasability of the ceramic green sheet. The release layer is also preferably a cured layer formed by curing the components contained in the release layer.

[0395] A release film or protective film (laminated film) obtained by laminating the present film and the release layer can suppress irregularities and is therefore particularly preferably applicable to release films for producing ceramic green sheets and semiconductors, which have been required to have a strict level of smoothness in recent years.

[0396] When an adhesive layer is laminated on the present film as a functional layer, a known adhesive can be used for the adhesive layer. Examples of the adhesive include rubber adhesives, acrylic adhesives, silicone adhesives, urethane adhesives, vinyl alkyl ether adhesives, polyvinyl pyrrolidone adhesives, polyacrylamide adhesives, and cellulose adhesives. Preferably, acrylic adhesives are used because of their excellent optical transparency and adhesive properties.

[0397] When a magnetic layer is stacked on the present film as a functional layer, the magnetic layer preferably contains ferromagnetic particles and a binder. Preferred ferromagnetic particles include ferromagnetic particles containing one or more metals selected from iron, cobalt, nickel, aluminum, yttrium and calcium.

[0398] When a hard coating layer is stacked on this film as a functional layer, the hard coating layer can be a known hard coating layer. The hard coating layer can be an inorganic layer composed of an inorganic substance, an organic layer composed of an organic substance, or a mixed layer comprising an inorganic substance and an organic substance. The hard coating layer is also preferably a cured layer.

[0399] [use]

[0400] This film can be used in various applications.

[0401] Examples of laminated films using the present film include the above-mentioned laminated films. The above-mentioned laminated films can be used for various purposes by commonly used methods.

[0402] For example, when the laminated film is a release film, it is preferably used as a release film (carrier film) for producing ceramic green sheets. Ceramic green sheets produced using the release film can be preferably used to produce ceramic capacitors that require multilayered internal electrodes as they become smaller and larger in capacity.

[0403] Furthermore, as described above, the release film having the present film can be used as a protective film for dry film resist, a release film for process manufacturing such as for semiconductor processes, and the like.

[0404] The method for manufacturing a ceramic green sheet using the release film is not particularly limited and can be implemented by a known method. As a method for manufacturing a ceramic green sheet, for example, the following method can be cited: applying the prepared ceramic slurry on the surface of the release layer of the release film, and drying to remove the solvent contained in the ceramic slurry.

[0405] The coating method of the ceramic slurry is not particularly limited, and for example, a known method such as a method of coating a ceramic slurry obtained by dispersing ceramic powder and a binder in a solvent by a reverse roll method and removing the solvent by heating and drying can be applied. The binder is not particularly limited, and for example, polyvinyl butyral can be cited. Furthermore, the solvent is not particularly limited, and for example, ethanol and toluene can be cited.

[0406] Example

[0407] Hereinafter, the present invention will be described in further detail based on examples.

[0408] The materials, usage amounts, ratios, treatment contents and treatment procedures shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be limitedly interpreted by the following examples.

[0409] [Film production]

[0410] First, the steps for producing the films used in the respective examples will be described.

[0411] The physical properties of each film and the methods for measuring the physical properties of the materials used to produce the film will be collectively described in the following section.

[0412] [Example 1]

[0413] <Extrusion molding process>

[0414] Using the titanium compound described in Japanese Patent No. 5575671 (citric acid chelated titanium complex, VERTEC AC-420, manufactured by Johnson Matthey) as a polymerization catalyst, polyethylene terephthalate particles were produced. After the obtained particles were dried to a moisture content of less than 50 ppm, they were put into the hopper of a twin-screw kneading extruder described in Japanese Patent No. 6049648, and then melted and extruded at 280°C. After the melt (melt) passed through a filter (pore size 3 μm), it was extruded from a die onto a cooling drum at 25°C, thereby obtaining an unstretched resin substrate composed of polyethylene terephthalate. In addition, the extruded melt (melt) was closely attached to the cooling drum by an electrostatic application method.

[0415] The polyethylene terephthalate constituting the unstretched resin substrate has a melting point (Tm) of 258°C and a glass transition temperature (Tg) of 80°C.

[0416] <Longitudinal Stretching Process>

[0417] The unstretched resin substrate was subjected to a longitudinal stretching step by the following method.

[0418] The preheated unstretched resin substrate was longitudinally stretched at a stretch ratio of 3.4 times and a stretching speed of 1300% / sec while the surface temperature was set to 90°C, thereby obtaining a uniaxially stretched resin substrate.

[0419] <Layer Formation Step>

[0420] The following composition A-1 (corresponding to composition A1) was applied on one side of a longitudinally stretched uniaxially stretched resin substrate (polyester substrate) using a bar coater, and the formed coating film was dried with hot air at 100° C., thereby forming a layer on one side of the uniaxially stretched resin substrate. In this step, the coating amount of composition A-1 was adjusted so that a resin layer having a thickness described below was formed in the finally manufactured biaxially oriented film.

[0421] (Composition A-1)

[0422] Composition A-1 was prepared by mixing the following components. The prepared composition A-1 was filtered using a filter with a pore size of 6 μm (F20, manufactured by MAHLE Filter Systems Japan Corporation) and subjected to membrane degassing (2×6 Radial Flow Super Phobic, manufactured by Polypore International Inc.), and then the obtained composition A-1 was applied to one surface of a uniaxially stretched resin substrate.

[0423] · Resin 1 (urethane resin, TAKELAC (registered trademark) W-605, manufactured by Mitsui Chemicals, Inc.) solid content concentration 25% aqueous dispersion: 157 parts by mass

[0424] · Anionic hydrocarbon surfactant (RAPISOL (registered trademark) A-90, sodium di-2-ethylhexyl sulfosuccinate, manufactured by NOF CORPORATION) with a solid content concentration of 1% by mass in water dilution: 56 parts by mass

[0425] · Particle 1 (non-crosslinked styrene resin particles (styrene copolymer), Nipol (registered trademark) UFN1008, manufactured by Zeon Corporation, average particle size 1.9 μm) solid content concentration 10% aqueous dispersion: 8 parts by mass

[0426] Water: 779 parts by mass

[0427] <Horizontal Stretching Process>

[0428] The resin substrate subjected to the longitudinal stretching step and the layer forming step was transversely stretched at a stretching ratio of 4.2 and a stretching speed of 50% / sec while keeping the surface temperature (temperature Y) at 120°C to obtain a biaxially oriented film.

[0429] The obtained biaxially oriented film was subjected to a heat setting process at 227°C for 6 seconds using a tenter. After the heat setting process, a heat relaxation process was carried out at 190°C and a heat relaxation rate Lr of 4%. In the heat relaxation process, the film width was reduced compared to the end of the heat setting process by reducing the distance between the holding parts of the tenter holding both ends of the film (the tenter width). The following heat relaxation rate Lr was calculated by the formula Lr = (L1-L2) / L1×100, based on the film width L2 at the end of the heat relaxation process relative to the film width L1 at the start of the heat relaxation process.

[0430] Then, cooling was performed at a cooling rate of 1500° C. / min. In the cooling step, the film width was expanded so that the expansion rate ΔL became 0.6%. In the cooling step, the film width was expanded by widening the tenter width to expand the film width compared to the end of the heat relaxation step.

[0431] The residence time from when the film is brought into the cooling section of the stretching machine to when it is brought out is defined as cooling time ta, and the temperature difference ΔT (°C) between the film surface temperature measured when brought into the cooling section and the film surface temperature measured when brought out of the cooling section is divided by the cooling time ta to obtain the following cooling rate.

[0432] Then, the following expansion ratio ΔL was calculated from the film width L3 at the end of the cooling process relative to the film width L2 at the start of the cooling process by the equation ΔL=(L3-L2) / L2×100.

[0433] The obtained biaxially oriented film was cut continuously along the conveying direction at positions 20 cm from both ends of the film in the width direction to trim both ends of the film. Then, an area of ​​10 mm in the width direction from both ends of the film was subjected to extrusion processing (knurling), and then the film was wound up at a tension of 40 kg / m.

[0434] The obtained biaxially oriented film had a thickness of 31 μm, a thickness of the resin layer of 60 nm, a width of 1.5 m, and a roll length of 7000 m. Protrusions having the shapes described in Table 1 were formed on the surface of the resin layer.

[0435] [Examples 2 to 5]

[0436] A biaxially oriented film was obtained in the same manner as in Example 1 except that the composition A-1 used in the layer forming step was replaced with the composition A-2 to A-5 in which the components were changed as shown in the table in the latter section, and the stretching temperature (temperature Y) in the transverse stretching step was changed as shown in the table in the latter section. In addition, the amount of each component of the composition A-2 to A-5 was adjusted to have the same solid content concentration as that of each component of the composition A-1. The details of the protrusions on the surface of the resin layer are shown in the table in the latter section.

[0437] In addition, the symbols in the table are as follows.

[0438] Resin 2 (urethane resin, HYDRAN (registered trademark) AP-40N, manufactured by DIC Corporation)

[0439] Resin 3 (urethane resin, SUPERFLEX (registered trademark) 210, manufactured by DKS Co. Ltd.)

[0440] Resin 4 (ester resin, Vylona (registered trademark) MD-1480, manufactured by TOYOBO CO., LTD., acid value 3 KOHmg / g)

[0441] [Example 6]

[0442] A biaxially oriented film was obtained in the same manner as in Example 1 except that the following composition A-6 was used instead of the composition A-1 used in the layer forming step. Details of the protrusions on the surface of the resin layer are shown in the table in the following section.

[0443] (Composition A-6)

[0444] Composition A-6 was prepared by mixing the following components. Composition A-6 was filtered and degassed in the same manner as composition A-1, and then the obtained composition A-6 was applied to the surface of a uniaxially stretched resin substrate.

[0445] · Resin 1 (urethane resin, TAKELAC (registered trademark) W-605, manufactured by Mitsui Chemicals, Inc.) solid content concentration 25% aqueous dispersion: 157 parts by mass

[0446] Anionic hydrocarbon surfactant (RAPISOL (registered trademark) A-90, manufactured by NOF CORPORATION) with a solid content concentration of 1% by mass Water dilution: 3δ parts by mass

[0447] · Particle 1 (non-crosslinked styrene resin particles, Nipol (registered trademark) UFN1008, manufactured by Zeon Corporation) solid content concentration 20 mass% aqueous dispersion: 11.2 mass parts

[0448] · A 25% by mass aqueous solution of crosslinking agent 1 (carbodiimide compound, CARBODILITE V-02-L2, manufactured by Nisshinbo Chemical Inc.): 32.2 parts by mass

[0449] Water: 622 parts by mass

[0450] [Examples 7 to 19]

[0451] A biaxially oriented film was obtained in the same manner as in Example 6 except that the composition A-6 used in the layer forming step was replaced with the composition A-7 to A-19 in which the components were changed as shown in the table in the latter section, and the stretching temperature (temperature Y) in the transverse stretching step was changed as shown in the table in the latter section. In addition, the amount of each component of the composition A-7 to A-19 was adjusted to have the same solid content concentration as that of the components of the composition A-6. The details of the protrusions on the surface of the resin layer are shown in the table in the latter section.

[0452] In addition, the symbols in the table are as follows.

[0453] Resin 5 (copolymer of methyl methacrylate / styrene / 2-ethylhexyl acrylate / 2-hydroxyethyl methacrylate / acrylic acid = 59:8:26:5:2 (mass ratio), Tg 34°C, acid value 10 mmol / g)

[0454] Resin 8 (aqueous dispersion of particles of an acid-modified olefin resin, ZAIKTHENE (registered trademark) NC, manufactured by Sumitomo Seika Chemicals Company, Limited)

[0455] Particles 2 (non-crosslinked polymethyl methacrylate (PMMA) resin particles, MP1000, manufactured by Soken Chemical & Engineering Co., Ltd., average particle size 0.4 μm)

[0456] Particle 3 (non-crosslinked styrene / acrylic acid copolymer resin particles, MP5000, manufactured by Soken Chemical & Engineering Co., Ltd., average particle size 0.4 μm)

[0457] Particle 4 (non-crosslinked styrene / acrylic acid copolymer resin particles, methyl methacrylate / styrene copolymer resin particles with a mass ratio of 70 / 30, average particle size 0.37 μm)

[0458] Particles 5 (non-crosslinked acrylic resin particles, methyl methacrylate / ethyl acrylate, acrylic acid copolymer resin particles with a mass ratio of 78 / 20 / 2, average particle size 0.35 μm)

[0459] Cross-linking agent 2 (oxazoline compound, EPOCROS (registered trademark) WS-700, manufactured by NIPPON SHOKUBAI CO., LTD.)

[0460] [Example 20]

[0461] A biaxially oriented film was obtained in the same manner as in Example 1 except that the following composition A-20 was used instead of the composition A-1 used in the layer forming step. Details of the protrusions on the surface of the resin layer are shown in the table in the following section.

[0462] (Composition A-20)

[0463] Composition A-20 was prepared by mixing the following components: Composition A-19 was filtered and degassed in the same manner as composition A-1, and then composition A-20 was applied to the surface of a uniaxially stretched resin substrate.

[0464] · Resin 3 (urethane resin, SUPERFLEX (registered trademark) 210, manufactured by DKS Co. Ltd.) solid content concentration 35% aqueous dispersion: 58 parts by mass

[0465] · Solid content concentration of resin 5 (copolymer of methyl methacrylate / styrene / 2-ethylhexyl acrylate / 2-hydroxyethyl methacrylate / acrylic acid = 59:8:26:5:2 (mass ratio)) 19 mass% aqueous dispersion: 105.8 mass parts

[0466] · Anionic hydrocarbon surfactant (RAPISOL (registered trademark) A-90, manufactured by NOF CORPORATION) with a solid content concentration of 1% by mass Water dilution: 12 parts by mass

[0467] · Particle 1 (non-crosslinked styrene resin particles, Nipol (registered trademark) UFN1008, manufactured by Zeon Corporation) solid content concentration 20 mass% aqueous dispersion: 11.2 mass parts

[0468] Aqueous solution of crosslinking agent 2 (oxazoline compound, EPOCROS (registered trademark) WS-700, manufactured by NIPPON SHOKUBAI CO., LTD.) with a solid content concentration of 25% by mass: 32.2 parts by mass

[0469] Water: 567 parts by mass

[0470] (Example 21)

[0471] A biaxially oriented film was obtained in the same manner as in Example 1 except that the following composition A-21 was used instead of the composition A-1 used in the layer forming step. Details of the protrusions on the surface of the resin layer are shown in the table in the following section.

[0472] (Composition A-21)

[0473] Composition A-21 was prepared by mixing the following components. Composition A-21 was filtered and degassed in the same manner as composition A-1, and then the obtained composition A-21 was applied to the surface of a uniaxially stretched resin substrate.

[0474] · Resin 3 (urethane resin, SUPERFLEX (registered trademark) 210, manufactured by DKS Co. Ltd.) solid content concentration 35% aqueous dispersion: 115 parts by mass

[0475] Anionic hydrocarbon surfactant (RAPISOL (registered trademark) A-90, manufactured by NOF CORPORATION) with a solid content concentration of 1% by mass Water dilution: 36 parts by mass

[0476] · Particle 1 (non-crosslinked styrene resin particles, Nipol (registered trademark) UFN1008, manufactured by Zeon Corporation) solid content concentration 20 mass% aqueous dispersion: 11.2 mass parts

[0477] · Particle 2 (PMMA resin particles, MP1000, manufactured by Soken Chemical & Engineering Co., Ltd.) solid content concentration 5 mass % aqueous dispersion: 179.2 mass parts

[0478] Aqueous solution of crosslinking agent 2 (oxazoline compound, EPOCROS (registered trademark) WS-700, manufactured by NIPPON SHOKUBAI CO., LTD.) with a solid content concentration of 25% by mass: 32.2 parts by mass

[0479] Water: 622 parts by mass

[0480] [Example 22]

[0481] A biaxially oriented film was obtained in the same manner as in Example 1 except that the following composition A-22 was used instead of the composition A-1 used in the layer forming step. Details of the protrusions on the surface of the resin layer are shown in the table in the following section.

[0482] (Composition A-22)

[0483] Composition A-22 was prepared by mixing the following components. Composition A-22 was filtered and degassed in the same manner as composition A-1, and then the obtained composition A-22 was applied to the surface of a uniaxially stretched resin substrate.

[0484] Resin 6 (urethane resin, ELASTRON (registered trademark) H3DF, manufactured by DKS Co. Ltd.) Aqueous solution having a solid content concentration of 28% by mass: 72 parts by mass

[0485] · Solid content concentration of resin 5 (copolymer of methyl methacrylate / styrene / 2-ethylhexyl acrylate / 2-hydroxyethyl methacrylate / acrylic acid = 59:8:26:5:2 (mass ratio)) 19 mass% aqueous dispersion: 105.8 mass parts

[0486] Anionic hydrocarbon surfactant (RAPISOL (registered trademark) A-90, manufactured by NOF CORPORATION) with a solid content concentration of 1% by mass Water dilution: 12 parts by mass

[0487] · Particle 1 (non-crosslinked styrene resin particles, Nipol (registered trademark) UFN1008, manufactured by Zeon Corporation) solid content concentration 20 mass% aqueous dispersion: 11.2 mass parts

[0488] · Particle 2 (PMMA resin particles, MP1000, manufactured by Soken Chemical & Engineering Co., Ltd.) solid content concentration 5 mass % aqueous dispersion: 134.4 mass parts

[0489] · Crosslinking agent 3 (blocked isocyanate compound, Duranate (registered trademark) WM44-L70, manufactured by Asahi Kasei Corporation) solid content 70% by mass dipropylene glycol dimethyl ether solution: 11.5 parts by mass

[0490] Water: 597 parts by mass

[0491] In addition, the solid content contained in the resin 6 is dissolved in water and does not exist in the form of particles.

[0492] [Example 23]

[0493] A biaxially oriented film was obtained in the same manner as in Example 22 except that the composition A-23 in which the components were changed as shown in the table in the latter section was used instead of the composition A-22 used in the layer forming step. In addition, the amount of each component of the composition A-23 was adjusted to have the same solid content concentration as that of the components of the composition A-22. The details of the protrusions on the surface of the resin layer are shown in the table in the latter section.

[0494] [Comparative Examples 1 and 2]

[0495] A biaxially oriented film was obtained in the same manner as in Example 1 except that the following composition C-1 or C-2 was used instead of the composition A-1 used in the layer forming step and the stretching temperature (temperature Y) in the transverse stretching step was changed as shown in the table in the following section. In addition, in the coating of the compositions C-1 and C-2, the coating amount was adjusted to 6 g / m 2 .

[0496] In the biaxially oriented films obtained in Comparative Examples 1 and 2, protrusions derived from the particles 4 or 6 were formed on the surface of the resin substrate, but no continuous resin layer was present. Details of the protrusions on the surface of the biaxially oriented film are shown in the table at the following stage.

[0497] (Composition C-1)

[0498] · Particle 4 (non-crosslinked styrene / acrylic acid copolymer resin particles, methyl methacrylate / styrene copolymer resin particles with a mass ratio of 70 / 30) solid content concentration 0.4 mass% aqueous dispersion: 157 mass parts

[0499] · Nonionic surfactant (NAROACTY CL95, manufactured by Sanyo Chemical Industries, Ltd.) 1 mass % aqueous solution: 70 mass parts

[0500] (Composition C-2)

[0501] · Aqueous dispersion of particles 6 (non-crosslinked acrylic resin particles, methyl methacrylate / ethyl acrylate, acrylic acid copolymer resin particles in a mass ratio of 78 / 20 / 2, average particle size 0.12 μm) adjusted to a solid content concentration of 0.4% by mass: 157 parts by mass

[0502] [Comparative Example 3]

[0503] A biaxially oriented film was obtained in the same manner as in Example 1 except that the following composition C-3 was used instead of the composition A-1 used in the layer forming step.

[0504] In the biaxially oriented film obtained in Comparative Example 3, a continuous resin layer was formed on the surface of the resin substrate, but no protrusions were formed. In addition, when the biaxially oriented film obtained in Comparative Example 3 was to be wound up, winding deviation occurred and it could not be wound up smoothly, so the evaluation of the formation of the functional layer in the later stage was not implemented.

[0505] (Composition C-3)

[0506] · Resin 1 (urethane resin, TAKELAC (registered trademark) W-605, manufactured by Mitsui Chemicals, Inc.) solid content concentration 25% aqueous dispersion: 81 parts by mass

[0507] · Solid content concentration of resin 5 (copolymer of methyl methacrylate / styrene / 2-ethylhexyl acrylate / 2-hydroxyethyl methacrylate / acrylic acid = 59:8:26:5:2 (mass ratio)) 19 mass% aqueous dispersion: 105.8 mass parts

[0508] Anionic hydrocarbon surfactant (RAPISOL (registered trademark) A-90, manufactured by NOF CORPORATION) with a solid content concentration of 1% by mass Water dilution: 12 parts by mass

[0509] Aqueous solution of crosslinking agent 2 (oxazoline compound, EPOCROS (registered trademark) WS-700, manufactured by NIPPON SHOKUBAI CO., LTD.) with a solid content concentration of 25% by mass: 32.2 parts by mass

[0510] Water: 622 parts by mass

[0511] [Comparative Example 4]

[0512] A biaxially oriented film was obtained in the same manner as in Example 1 except that the following composition C-4 was used instead of the composition A-1 used in the layer forming step and the stretching temperature (temperature Y) in the transverse stretching step was changed as shown in the table in the following section. Details of the protrusions on the surface of the resin layer are shown in the table in the following section.

[0513] (Composition C-4)

[0514] · Resin 7 (acrylic resin, copolymer of methyl methacrylate / stearyl methacrylate / hydroxyethyl methacrylate / methacrylic acid in a mass ratio of 47 / 26 / 20 / 7) with a solid content concentration of 20% by mass Aqueous dispersion: 165 parts by mass

[0515] Fluorine-based surfactant (Surflon (registered trademark) S-211, manufactured by AGC SEIMI CHEMICAL CO., LTD.) with a solid content concentration of 1% by mass Water dilution: 30 parts by mass

[0516] · Particle 7 (cross-linked acrylic particles, manufactured by NIPPON SHOKUBAI CO., LTD., trade name MX100W) solid content concentration 10% aqueous dispersion: 23.7 parts by mass

[0517] Aqueous solution of crosslinking agent 2 (oxazoline compound, EPOCROS (registered trademark) WS-700, manufactured by NIPPON SHOKUBAI CO., LTD.) with a solid content concentration of 25% by mass: 56.8 parts by mass

[0518] Water: 750 parts by mass

[0519] exist Figure 2 The image of the surface of the resin layer of the biaxially oriented film produced by a method similar to that of the embodiment is shown in FIG. Figure 3 9 shows an image of the surface of the resin layer of the biaxially oriented film produced by a method similar to that of Comparative Example 4 observed by SEM.

[0520] like Figure 2 As shown in FIG. 1 , it was observed that in the protrusions existing on the surface of the resin layer of the biaxially oriented film produced by a method similar to that of the embodiment, as described later, the ratio of the height of the protrusion to the major axis of the protrusion was small. Figure 3 It was observed that the protrusions existing on the resin layer surface of the biaxially oriented film produced by a method similar to that of the comparative example had clear contours and a shape close to a spherical shape, and as described later, the ratio of the height of the protrusion to the major axis of the protrusion was large.

[0521] [Measurement methods of physical properties, etc.]

[0522] 〔Thickness of resin layer〕

[0523] The thickness of the resin layer was measured by the following procedure.

[0524] First, the obtained film was cut with a microtome to expose the cross section of the film in the thickness direction. The exposed film cross section was polished with Ar ions to make the film cross section smooth, and then Pt was evaporated on the film cross section to obtain an observation sample. The observation sample was observed with a SEM ("S-4800" manufactured by Hitachi High-Tech Corporation), and the thickness of the resin layer in the film cross section was measured by the above method.

[0525] [Thickness of film]

[0526] The film thickness was measured by the above-mentioned method using a continuous stylus film thickness meter.

[0527] 〔Glass transition temperature〕

[0528] The glass transition temperatures (Tg) of the particles and resins used in Examples and Comparative Examples were measured using a differential scanning calorimeter in the following procedure.

[0529] Specifically, a differential scanning calorimeter (DSC2500 manufactured by TA Instruments) was used, 5 mg of the powder sample was placed in a sealed pan of the differential scanning calorimeter, and the temperature was measured at a heating rate of 5°C / min in the range of -50 to 300°C. The temperature modulation conditions were set to ±0.5°C / min and a cycle of 60 seconds. Tg uses the measurement results of the second cycle of heating, and the peak value in the curve of the first-order differential of the reversing heat flow is adopted as Tg. In addition, when the particles or resins used in the embodiments and comparative examples are dispersions or solutions, the powder obtained by drying at a high temperature in the range of 100 to 300°C and lower than the thermal decomposition temperature of the resin is used as the above-mentioned powder sample.

[0530] [Protrusion height, protrusion major diameter and protrusion minor diameter]

[0531] After marking the surface of the resin layer of the film with a felt pen, platinum was evaporated to obtain a sample for observation. Using SEM ("S4700", manufactured by Hitachi High-Tech Corporation), the vicinity of the mark on the surface of the resin layer was photographed at a low magnification from the vertical direction of the sample surface. The protrusion with the longest long diameter among the protrusions existing in the observation area (measurement field of view) of 100μm×100μm was selected, and the protrusion was photographed at a higher magnification to measure the long diameter (maximum diameter in the in-plane direction) and short diameter of the protrusion.

[0532] Next, the marked portion was measured under the following measurement conditions using an optical interferometer (Vertscan 3300G Lite, manufactured by Hitachi High-Tech Corporation) to confirm the distribution of the protrusions. The distribution was compared with the observation results in the SEM, and the protrusions observed in the SEM were identified. After the protrusions were identified, the protrusion cross-section was observed by two-dimensional analysis to measure the height of the protrusions.

[0533] Based on the measured major diameter and height of the protrusion, the ratio of the determined height of the protrusion to the major diameter of the protrusion is calculated.

[0534] (Measurement conditions)

[0535] ·Measurement mode: WAVE mode

[0536] Objective lens: 50 times

[0537] ·Measurement area: 186μm×155μm

[0538] By the above method, the long diameter of the protrusion and the height corresponding to the protrusion are measured in 10 different observation areas on the surface of the resin layer of the sample, and the ratio of the height of the protrusion to the long diameter of the protrusion is calculated. The arithmetic mean of the ratios calculated for each observation area is used as the ratio of the height of the protrusion to the long diameter of the protrusion, and is recorded as "Ratio A" in the table.

[0539] Furthermore, the long and short axes of the protrusions obtained for each observation area and the arithmetic mean values ​​of the height corresponding to the protrusions were used as the protrusion height, the long axis of the protrusions, and the short axis of the protrusions. The ratio of the long axis of the protrusion to the short axis of the protrusions (ratio of the long axis of the protrusions / the short axis of the protrusions) was calculated based on the long axis of the protrusions and the short axis of the protrusions obtained.

[0540] 〔Number of protrusions〕

[0541] In the sample produced when measuring the protrusion height, protrusion major axis and protrusion minor axis, the vicinity of the mark on the surface of the resin layer was observed using SEM ("S4700", manufactured by Hitachi High-Tech Corporation). The observation was performed in the observation area (measurement field of view) of the above area, and the number of protrusions present was counted. The number of protrusions was counted in 10 different observation areas on the surface of the resin layer, and the arithmetic mean was calculated and used as the number of protrusions.

[0542] 〔Surface free energy〕

[0543] The surface free energy of the surface on the resin layer side of the film (second main surface) was measured by the following method.

[0544] Using a contact angle meter (DROPMASTER-501 manufactured by Kyowa Interface Science Co., Ltd.), droplets were dripped onto the resin layer surface of the manufactured film at 25°C, and the contact angle was measured 1 second after the droplets adhered to the surface. 2 μL of pure water, 1 μL of diiodomethane, and 1 μL of ethylene glycol were used as droplets, and the surface free energy (unit: mJ / m) was calculated based on the measured contact angles using the method of Kitazaki Hata. 2 ).

[0545] In addition, the "surface free energy" obtained by the above method is the total of the polar component and the hydrogen bond component of the surface free energy.

[0546] [evaluate]

[0547] The laminated films shown below were prepared and evaluated. That is, while conveying the films obtained in the examples and comparative examples, a functional layer was arranged on one surface of the films, and the obtained films (laminated films) were rolled up, and then the uneven defects on the surface of the functional layer were evaluated when unrolling.

[0548] 〔Production and evaluation of release film〕

[0549] <Preparation of coating solution for forming release layer>

[0550] With reference to Preparation Example 1 of Japanese Patent Application Laid-Open No. 2015-195291, hexamethylene diisocyanate, dimethyl organopolysiloxane and dipentaerythritol pentaacrylate (ARONIX (registered trademark) M-400, manufactured by TOAGOSEI CO., LTD.) were reacted to synthesize a curable silicone compound (A1). Next, 100 parts by mass of the curable silicone compound (A1) and 5 parts by mass of 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]-phenyl}-2-methyl-propan-1-one (manufactured by IGM Resins BV, product name "Omnirad127") as a photopolymerization initiator (B1) were diluted to a solid content concentration of 20% by mass in a mixed solvent of isopropyl alcohol and methyl ethyl ketone (mass ratio 3:1), to obtain a coating liquid for forming a release layer.

[0551] <Production of Release Film>

[0552] The film rolls prepared in the examples and comparative examples were placed in an environment of 25°C and 50%RH for 1 week. The film rolls were unrolled and coated with the peeling layer forming composition prepared in the above step while transferring it to the film surface opposite to the surface where the resin layer was located, and dried at 80°C for 1 minute. The coating amount of the peeling layer was adjusted so that the thickness after curing would be 1μm. Then, ultraviolet rays (irradiation amount: 250mJ / cm 2 ), the coating liquid for forming a release agent layer is cured to form a release layer, thereby obtaining a release film (laminated film).

[0553] The obtained release films were evaluated as follows.

[0554] (Coiling properties)

[0555] The obtained release film was conveyed at a line speed of 100 m / min and a tension of 7 kg / m, and was wound around a 6-inch (1 inch = 2.54 cm) diameter ABS (acrylonitrile-butadiene-styrene) resin core while being pressed with a touch roller at a pressure of 30 kg / m, and the release film having a length of 7000 m in the longitudinal direction was wound into a roll. The rubber hardness of the touch roller measured with an A-type hardness meter was 60 degrees.

[0556] The wound-up release film was visually observed, and the windability during high-speed transport was evaluated based on the observation results and the following evaluation criteria.

[0557] (Evaluation criteria for coiling performance)

[0558] A: No winding deviation was observed at all.

[0559] B: Winding deviation occurs slightly, but is within an allowable level.

[0560] C: Winding deviation occurs.

[0561] (Solvent resistance)

[0562] The resin layer surface of the obtained release film was subjected to a load of 1000 g / cm2 using a cloth containing a mixed solution of methyl ethyl ketone and toluene (mass ratio 1:1). 2 The film was rubbed 5 times in the longitudinal direction and 5 times in the transverse direction. Then, the surface of the resin layer was visually observed, and the solvent resistance was evaluated based on the dissolution state of the resin layer. The evaluation criteria were as follows.

[0563] A: The resin layer was not dissolved at all.

[0564] B: The resin layer is partially dissolved.

[0565] C: The resin layer is completely dissolved.

[0566] (Concave-convex defects (evaluation 1))

[0567] A release film was rolled out from the release film roll evaluated for winding at high speed. The release layer surface of the rolled out release film was visually inspected under a three-wavelength fluorescent lamp, and the reflected light of the fluorescent lamp was observed to confirm the presence of uneven defects.

[0568] (Evaluation criteria for uneven defects)

[0569] A: No uneven defects were found on the peeling layer surface

[0570] B: Concavo-convex defects are confirmed on the surface of the peeling layer

[0571] 〔Concave and convex defects (evaluation 2)〕

[0572] The unevenness defects of the release film were evaluated in the same manner as the unevenness defects (Evaluation 1) except that a film roll having a storage period changed to 3 months was used in the production step of the release film.

[0573] (Evaluation criteria for uneven defects)

[0574] A: No uneven defects were found on the peeling layer surface

[0575] B: 1 to 5 concave and convex defects are confirmed on the surface of the peeling layer

[0576] C: Six or more concave-convex defects are confirmed on the surface of the peeling layer

[0577] Table 1 shows the evaluation results of the release films.

[0578] In addition, as described above, in Comparative Example 3, since the above-mentioned evaluation was not performed, the evaluation column is set to "-".

[0579]

[0580] From the results in Table 1, it was confirmed that when the film includes a resin layer and the ratio of the height of the protrusions on the surface of the resin layer to the major axis of the protrusions (ratio A) is 0.70 or less, the uneven defects of the functional layer can be suppressed.

[0581] On the other hand, in Comparative Examples 1 and 2 not including a resin layer and Comparative Example 4 in which the ratio of the height of the protrusions on the surface of the resin layer to the major axis of the protrusions exceeded 0.70, the unevenness defects of the functional layer could not be suppressed.

[0582] Comparison between Examples 1 to 4 and 9 and Example 5 confirmed that when the resin layer contains at least one binder selected from acrylic resins, urethane resins, and olefin resins, unevenness defects during long-term storage are further suppressed.

[0583] Comparison between Examples 6 to 22 and Examples 1 to 5 confirmed that when the composition used for forming the resin layer contains a crosslinking agent, that is, when the resin layer is a crosslinked film, the resin layer has excellent solvent resistance.

[0584] 〔Production and evaluation of decorative films〕

[0585] The film produced in Example 22 was used as a support, and a decorative transfer film (decorative film) was produced by the following procedure.

[0586] The thermoplastic (non-photosensitive) resin layer coating liquid described in

[0106] of the International Publication No. 2017 / 208849 specification is applied to the surface of the film produced in Example 22 on the side opposite to the resin layer side, and dried at 80°C to form a thermoplastic (non-photosensitive) resin layer. Next, the base layer coating liquid described in

[0189] of the International Publication No. 2021 / 261412 specification is applied and dried at 120°C to form a base layer. A photosensitive resin layer forming composition described in

[0202] of the International Publication No. 2021 / 261412 specification is applied thereon and dried at 90°C to form a photosensitive resin layer (decorative layer). The thickness of the base layer is 1.6 μm, and the thickness of the photosensitive resin layer is 2.0 μm.

[0587] The above-mentioned decorative transfer film was produced while the film was being conveyed.

[0588] The surface of the decorative transfer film (the surface of the decorative layer on the side opposite to the support) that was rolled out after the decorative transfer film was wound up under the same conditions as the release film was evaluated in the same manner as the release layer (concave-convex defects (evaluation 1)). As a result, no concave-convex defects were observed in the decorative layer.

[0589] Furthermore, by using the obtained decorative transfer film, a decorative pattern was formed according to the description of

[0109] of the specification of International Publication No. 2017 / 208849, and a pattern with a good shape could be formed.

[0590] 〔Production and evaluation of functional material films〕

[0591] The following ceramic slurry was applied to the surface of the film produced in Example 22 on the side opposite to the resin layer to a thickness of 1 μm and dried at 80° C. for 1 minute to produce a film with a ceramic green sheet (functional material film).

[0592] The above-mentioned film with ceramic green sheet was produced while the film was conveyed.

[0593] (Preparation of ceramic slurry)

[0594] A mixed solution was prepared by mixing 100 parts by mass of barium titanate powder (BaTiO3; manufactured by Sakai Chemical Industry Co., Ltd., product name "BT-03"), 8 parts by mass of polyvinyl butyral resin (manufactured by SEKISUI CHEMICAL CO., LTD., product name "S-LEC (registered trademark) B·K BM-2") as a binder, 4 parts by mass of dioctyl phthalate (manufactured by KANTOCHEMICAL CO., INC., dioctyl phthalate, extra pure) as a plasticizer, and 135 parts by mass of a mixed solution of toluene and ethanol (mass ratio 6:4). Zirconia beads were added to the mixed solution, and the mixture was dispersed in the barium titanate powder mixed solution using a ball mill to prepare a dispersion. The zirconium oxide beads were removed from the obtained dispersion to prepare a ceramic slurry.

[0595] The ceramic green sheet obtained by winding up the film with ceramic green sheet under the same conditions as the peeling film was subjected to the same evaluation as the peeling layer (concavoconvex defects (evaluation 1)). As a result, no concavoconvex defects were observed on the ceramic green sheet.

Claims

1. A film comprising a resin substrate and a resin layer, The resin layer has protrusions on its surface, The ratio of the height of the protrusion to the major diameter of the protrusion is 0.70 or less.

2. The film according to claim 1, wherein The protrusions include a non-polyester resin.

3. The film according to claim 1, wherein The protrusions include at least one of an acrylic resin and a styrene resin.

4. The film according to claim 1, wherein The resin layer is a single-layer coating layer.

5. The film according to claim 1, wherein The resin layer includes at least one adhesive selected from acrylic resins, urethane resins, and olefin resins.

6. The film according to claim 5, wherein The binder includes a resin having an acid group.

7. The film according to claim 1, wherein The resin layer is a cross-linked film.

8. The film according to claim 1, wherein The thickness of the resin layer is 0.01 μm to 1 μm.

9. The film according to claim 1, wherein The protrusions are 10000 μm above the surface of the resin layer. 2 There are more than 50 in the area.

10. The film according to claim 1, wherein The ratio of the major diameter of the protrusion to the minor diameter of the protrusion exceeds 1.

60.

11. A laminated film comprising the film according to any one of claims 1 to 10 and a functional layer, The laminated film comprises the resin layer, the resin substrate and the functional layer in this order, The functional layer is one selected from a decorative layer, a photosensitive resin layer, an inorganic layer and a peeling layer.

12. A method for producing a film, comprising the following steps: A step of forming a layer on at least one surface of a resin substrate using a composition comprising non-crosslinked resin particles A, resin B, and a solvent; and a step of stretching the resin substrate on which the layer is formed while heating it at a temperature Y, The film manufacturing method satisfies the following requirements 1 and 2. Requirement 1: The value obtained by subtracting the glass transition temperature of the non-crosslinked resin particles A from the temperature Y is -20°C to 50°C; Requirement 2: When the resin B is present in the composition in the form of particles, the particle size of the resin B in the form of particles is smaller than the particle size of the non-crosslinked resin particles A.

13. The method for producing a film according to claim 12, wherein: The resin substrate is a uniaxially stretched resin substrate obtained by stretching an unstretched resin substrate.

14. The method for producing a film according to claim 12 or 13, wherein: The resin B is a resin having an acid group, and the composition further comprises a cross-linking agent.

15. The method for producing a film according to claim 12 or 13, wherein: The non-crosslinked resin particles A have a glass transition temperature of 70°C to 140°C.

16. The method for producing a film according to claim 12 or 13, wherein: The glass transition temperature of the resin B is -50°C to 105°C.

17. The method for producing a film according to claim 12 or 13, wherein: When the resin B is present in the composition in the form of particles, the particle size of the resin B is set to Db μm, and the particle size of the non-crosslinked resin particles A is set to Da, the relationship of formula (1) is satisfied. Formula (1) 7×Db <Da。

Citation Information

Patent Citations

  • Background value eliminating method for gas monitor and its unit

    JP1980075671A

  • Master slice IC

    JP1985049648A

  • Laminated film and method for producing the same

    JP2014076632A

  • Transfer film and transparent laminate, method for manufacturing the same, electrostatic capacitive input device and image display device

    JP2014108541A

  • Polyester film and method for manufacturing the same

    JP2014189002A